Abrasion-Induced Acceleration of Melt Crystallisation of Wet Comminuted Polybutylene Terephthalate (PBT) - Tischer, Florentin; Düsenberg, Björn; Gräser, Timo; Kaschta, Joachim; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2022)
Within this contribution, the effect of grinding media wear on the melt crystallisation of polybutylene terephthalate (PBT) is addressed. PBT was wet ground in a stirred media mill in ethanol using different grinding media beads (silica, chrome steel, cerium-stabilised and yttrium-stabilised zirconia) at comparable stress energies with the intention to use the obtained particles as feed materials for the production of feedstocks for laser powder bed fusion additive manufacturing (PBF-AM). In PBF‑AM, the feedstock’s optical, rheological and especially thermal properties—including melt crystallisation kinetics—strongly influence the processability and properties of the manufactured parts. The influence of process parameters and used grinding media during wet comminution on the optical properties, crystal structure, molar mass distribution, inorganic content (wear) and thermal properties of the obtained powders is discussed. A grinding media-dependent acceleration of the melt crystallisation could be attributed to wear particles serving as nuclei for heterogeneous crystallisation. Yttrium-stabilised zirconia grinding beads proved to be the most suitable for the production of polymer powders for the PBF process in terms of (fast) comminution kinetics, unchanged optical properties and the least accelerated crystallisation kinetics.<br
Keywords: wet comminution; stirred media mills; abrasion; polymer; additive manufacturing; powder bed fusion; thermal properties; isothermal DSC

A comparative study of mechanical properties of table tennis balls - Hiemer, Stefan; Fey, Tobias; Kaschta, Joachim; Schubert, Dirk W. (54th Nordic Polymer Days, 2017)

Alginate-based hydrogels with improved adhesive properties for cell encapsulation - Sarker, Bapi; Rompf, Julia; Silva, Raquel; Lang, Nadine; Detsch, Rainer; Kaschta, Joachim; Fabry, Ben; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2015)
Hydrogel-based biomaterials are ideal scaffolding matrices for microencapsulation, but they need to be modified to resemble the mechanical, structural and chemical properties of the native extracellular matrix. Here, we compare the mechanical properties and the degradation behavior of unmodified and modified alginate hydrogels in which cell adhesive functionality is conferred either by blending or covalently cross-linking with gelatin. Furthermore, we measure the spreading and proliferation of encapsulated osteoblast-like MG-63 cells. Alginate hydrogels covalently crosslinked with gelatin show the highest degree of cell adhesion, spreading, migration, and proliferation, as well as a faster degradation rate, and are therefore a particularly suitable material for microencapsulation.
Keywords: Alginate; Cell encapsulation; Hydrogel

A method to reveal bulk and surface crystallinity of Polypropylene by FTIR spectroscopy - Suitable for fibers and nonwovens - Lanyi, Franz; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W. (Polymer Testing, 2018)
Keywords: X-ray diffraction; Isotactic Polypropylene; Processing; Crystallinity; Fourier-transform infrared spectroscopy; Fiber spinning

Analysis of gel from silicone breast implants made by Poly Implant Prothese and other manufactures - Schubert, Dirk W.; Horch, Raymund E.; Kaschta, Joachim (13th Bayreuth Polymer Symposium, 2013)

Avoiding waviness of relaxation spectra - Kaschta, Joachim; Stadler, Florian (Rheologica Acta, 2009)
Spectra are material functions, whose different integral transforms yield the measurable rheological quantities in the linear viscoelastic regime. Therefore, their knowledge is of high fundamental interest. However, the calculation of spectra from experimental data is an ill-posed problem. Thus, it is hampered by the problem that a too low density of relaxation modes does not lead to a good description of the input data, while a higher one usually causes a wavy spectrum which cannot be interpreted. To overcome this problem, an additional criterion assuming only gradual changes in the spectrum is introduced allowing for an increase in mode density without an enhanced waviness of the spectrum. This is novel in comparison to previously published spectra algorithms and commercial software packages.
Keywords: Relaxation spectrum; Error minimization; Spectrum shape

Biaxial Elongation Behavior in Partially Molted State of Two-Layer Sheets Containing Postconsumer Material - Wittmann, Lisa-Maria; Kaschta, Joachim; Drummer, Dietmar (Polymers, 2022)
Due to the lack of raw material and forced by political demand, an increasing percentage of postconsumer materials (PCR) shall be used in all processing methods in polymer technology. Thermoforming, as one of the oldest polymer-processing methods, has special requirements regarding the melt stability at high temperatures. Low melt stability affects the thermoforming in a negative manner, as the low stiffness leads the sheet to sag during the heating phase. In this study, two-layer sheets are used in order to improve melt stability of PCR material. The focus is placed on the influence of rheological properties on the biaxial stretching behavior of mono- and two-layer sheets in partially molted state. In order to create a stabilizing layer, two different thermoformable virgin materials with a melt flow rate (MFR) of 3 g/10 min and 6 g/10 min were chosen. The second layer consists of instable PCR materials with a MFR of 16 g/10min and 50 g/10 min. Rheological investigations, molecular characterization and biaxia tretching tests are used to show the benefit of two-layer sheets for processing PCR material under elongational stress. The results show that the use of two-layer sheets can improve the biaxial stretching properties, so that two-layer sheets can offer a significant potential in the processing of PCR materials in thermoforming.<br

Binary and Ternary Blends of Polypropylene Types-Influence on the Homogeneity of Biaxial Oriented Films - Schubert, Dirk W.; Kaschta, Joachim; Seidl, Stephan; Kunzelmann, Peter (Polychar 23rd, 2015)

Binary and Ternary Blends of Polypropylene Types – Influence on the Homogeneity of Biaxial-Oriented Films - Schubert, Dirk W.; Kaschta, Joachim; Seidl, Stephan; Kunzelmann, Peter (Macromolecular Symposia, 2016)
Biaxial-oriented polypropylene (BOPP) is one of the most used materials for industrial films and food packaging. In terms of environmental and economic issues, the reduction of the film thickness, increasing the homogeneity, enhancing the process efficiency and stability are in the focus of this work. A systematic investigation on the biaxial stretching process is presented in this study. Therefore, two commercial linear polypropylenes with different molar masses and a commercial long-chain-branched polypropylene were used to obtain binary and ternary blends to adjust the elongation behavior on the molecular level. The blending was carried out using a cast film process on a twin-screw extruder. The cast films obtained, were investigated before and after biaxial stretching. The thickness distribution of the films, were used as a measure of the film homogeneity, before and after the film stretching process. It turns out that casting and biaxial stretching are competing steps with respect to the film homogeneity. The casting step is dominated by the extrusion behavior of the blends. With increasing amount of the long-chain branched material extrusion flow instabilities appear leading to an irregular surface and to a poor film homogeneity. Contrarily, long-chain branches promote a more homogeneous deformation during the biaxial stretching inducing strain hardening which leads to a self-healing effect and thus to an improved film homogeneity. The homogeneity of the final stretched film depends on both, casting and stretching. Therefore, a desirable polymer blend recipe with a medium amount of long-chain branches is revealed for the stretched film.
Keywords: blends; BOPP films; film homogeneity; film stretching; linear and branched molecules

Characterisation of Magneto-Sensitive Elastomers; Material Model meets Experimental Results - Walter, Bastian; Saxena, Prashant; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (13th Bayreuth Polymer Symposium, Bayreuth, 2013)

Characterization of branched ultrahigh molar mass polymers by asymmetrical flow field-flow fractionation and size exclusion chromatography - Otte, Tino; Stadler, Florian; Kaschta, Joachim; Becker, Florian; Buback, Michael; et al. (Journal of Chromatography A, 2011)
The molar mass distribution (MMD) of synthetic polymers is frequently analyzed by size exclusion chromatography (SEC) coupled to multi angle light scattering (MALS) detection. For ultrahigh molar mass (UHM) or branched polymers this method is not sufficient, because shear degradation and abnormal elution effects falsify the calculated molar mass distribution and information on branching. High temperatures above 130 degrees C have to be applied for dissolution and separation of semi-crystalline materials like polyolefins which requires special hardware setups. Asymmetrical flow field-flow fractionation (AF4) offers the possibility to overcome some of the main problems of SEC due to the absence of an obstructing porous stationary phase. The SEC-separation mainly depends on the pore size distribution of the used column set. The analyte molecules can enter the pores of the stationary phase in dependence on their hydrodynamic volume. The archived separation is a result of the retention time of the analyte species inside SEC-column which depends on the accessibility of the pores, the residence time inside the pores and the diffusion ability of the analyte molecules. The elution order in SEC is typically from low to high hydrodynamic volume. On the contrary AF4 separates according to the diffusion coefficient of the analyte molecules as long as the chosen conditions support the normal FFF-separation mechanism. The separation takes place in an empty channel and is caused by a cross-flow field perpendicular to the solvent flow. The analyte molecules will arrange in different channel heights depending on the diffusion coefficients. The parabolic-shaped flow profile inside the channel leads to different elution velocities. The species with low hydrodynamic volume will elute first while the species with high hydrodynamic volume elute later. The AF4 can be performed at ambient or high temperature (AT-/HT-AF4). We have analyzed one low molar mass polyethylene sample and a number of narrow distributed polystyrene standards as reference materials with known structure by AT/HT-SEC and AT/HT-AF4. Low density polyethylenes as well as polypropylene and polybutadiene, containing high degrees of branching and high molar masses, have been analyzed with both methods. As in SEC the relationship between the radius of gyration (R(g)) or the molar mass and the elution volume is curved up towards high elution volumes, a correct calculation of the MMD and the molar mass average or branching ratio is not possible using the data from the SEC measurements. In contrast to SEC. AF4 allows the precise determination of the MMD, the molar mass averages as well as the degree of branching because the molar mass vs. elution volume curve and the conformation plot is not falsified in this technique. In addition, higher molar masses can be detected using HT-AF4 due to the absence of significant shear degradation in the channel. As a result the average molar masses obtained from AF4 are higher compared to SEC. The analysis time in AF4 is comparable to that of SEC but the adjustable cross-flow program allows the user to influence the separation efficiency which is not possible in SEC without a costly change of the whole column combination. (C) 2011 Elsevier B.V. All rights reserve
Keywords: Polyethylene; Polybutadiene; Polypropylene; Polystyrene; Field-flow fractionation; Light scattering; Size exclusion chromatography; Ultrahigh molar masses; Branching; Shear degradation

Characterization of polyethylene of raised temperature resistance (PE-RT) materials - a mini review and insights - Schneider, Nicolai; Kaschta, Joachim; Heiduk, Ines; Schubert, Dirk W. (Nordic Polymer Days 2023, 2023)
Since the development of the first pipe sys- tems over 5500 years ago, various materials in- cluding terracotta, metals and polymers, were used in this field of application. High-density polyethylens (HDPE) display good processabil- ity and chemical resistance at low costs since their first pipe application in 1954 [1, 2]. Polyethylenes in long-term high temperature implementations tend to failure mechanisms such as slowcrack-growth (SCG) and environmental-stress-cracking (ESC). In both failure mechanisms, long-term stresses lead to the formation of so-called craze-structures, where crystals rotate in stress direction with an alternating pattern of crystalline and amor- phous segments (fibrills) between accruing voids, promoted by raised temperatures. The cohesion of crystallites within the craze is main- ly assured by tiemolecules, amorphous chains that are incorporated in several crystallites, forming intercrystalline bridges [3]. Therefore, creep resistant materials such as cross-linked polyethylene (PE-X) and polyethylene of raised temperature resistance (PE-RT) were invented to impede the failure in the amorphous regions. In the case of PE-RTs, the macromolecules in the high molecular mass fractions are short- chain branched by multistep polymerisation with α-olefins. Consequently, their crystalli- zation is hindered. The crystalline matrix is formed by the almost linear low molar mass fractions, whereas the highbranched high molecular mass fractions are incorporated in multiple crystals and so form tie-molecules. This work reviews several methods to char- acterize those polyethylenes with respect to their comonomer distribution and tie mole- cule density. Due to the necessity to locate the comonomer solely on the long chains, polymers will be separated by means of their molar mass by chemical precipitation frac- tionation or by successive self-nucleation and annealing treatment (SSA). The precipitates molar mass distributions are subsequently analysed by high temperature gel permeation chromatography (HT-GPC) measurements. The comonomer content and is determined by Fourier-transform infrared spectroscopy (FTIR), whereas the SSA spectrum provides informa- tion about the intra-fractional distribution of the comonomer. The long-term performance of such materials can be estimated by the measurement of their strain hardening modu- lus (SH-Modulus) at elevated temperature [

Characterization of the temperature and frequency dependency of the complex Poisson’s ratio using a novel combined torsional-axial rheometer - Rodríguez Agudo, José Alberto; Haeberle, Jan; Müller-Pabel, Michael; Troiss, Alexander; Shetty, Abhishek; Kaschta, Joachim; Giehl, Christopher (Journal of Rheology, 2023)
This study discusses the feasibility of using a combined torsional-axial rheometer to indirectly measure the complex Poisson’s ratio based on shear and Young’s modulus. For this purpose, isothermal frequency sweeps in torsion and extension are performed sequentially on the same cylindrical specimen and under the same environmental conditions. The method is tested on two amorphous polymers, a semicrystalline polymer, a polymer blend, and a copolymer. The article includes an extensive literature review and an uncertainty assessment of the method to provide a basis for subsequent data comparison with existing research. The experimental data show a monotonic increase in the complex Poisson’s ratio up to 0.5 as the temperature approaches α-relaxation for all samples, except for the amorphous polymer. The latter shows a local minimum in the complex Poisson’s ratio observed near α-relaxation, which disappears after thermal annealing of the sample above the α-relaxation temperature. The real and imaginary parts of the complex Poisson’s ratio are additionally determined by evaluating both phase shift angles from torsional and extensional measurements. All polymers show a certain offset between the torsional and extensional phase shift angles in the glassy state, which gradually decreases as the temperature approaches α-relaxation. The complex Poisson’s ratio results are in good agreement with the literature data obtained by existing methods. This confirms that the method is applicable to polymers up to α-relaxation temperatures with significant time savings due to the nondestructive approach. This is of particular interest, given the limited availability of data in the literature.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Acrylonitrile butadiene styrene; Dynamic mechanical analysis; Glass transition temperature; Poisson’s ratio; Polycarbonate; Polymer testing; Polymethylmethacrylate; Polypropylene; Rheology; Thermal annealing; Thermoplastic Polyurethane; Viscoelasticity

Comparative Rheological Studies of Autoclave and Tubular Low-Density Polyethylene - Wang, Hao; Kaschta, Joachim; Schubert, Dirk W. (29th International Conference of the Polymer Processing Society, 2013)

Comparing recycled and virgin poly (ethylene terephthalate) melt-spun fibres - Qin, Yijing; Qu, Muchao; Kaschta, Joachim; Schubert, Dirk W. (Polymer Testing, 2018)
Keywords: Virgin PET; Mechanical properties; Recycled PET; Melt spinning

Comparing recycled and virgin poly(ethyleneterephthalate) melt-spun fibres - Qin, Yijing; Qu, Muchao; Kaschta, Joachim; Schubert, Dirk W. (Annual European Rheology Conference (AERC2019), 2019)

Comparison of viscous and elastic properties of polyolefin melts in shear and elongation - Wolff, Friederich; Resch, Julia; Kaschta, Joachim; Münstedt, Helmut (Rheologica Acta, 2010)
Viscous and elastic properties of a linear polypropylene (PP) and a long-chain branched low-density polyethylene (LDPE) have been investigated by creep and creep-recovery experiments in shear and elongation. The data obtained verify the ratios between the linear values of the viscosities and the steady-state elastic compliances in shear and elongation predicted by the theory of linear viscoelasticity. In the nonlinear range, no simple correlation between the viscous behaviour in shear and elongation exists. The elongational viscosity of the PP decreases with increasing stress analogously to the shear thinning observed; the linear range extends to higher stresses in elongation than in shear, however. The LDPE shows thinning in shear and strain hardening in elongational flow. For the LDPE, a linear steady-state elastic tensile compliance corresponding to one third of the linear steady-state elastic compliance in shear was determined. For the PP, this theoretically predicted value is approximately reached. Analogous to the viscous behaviour, the linear range extends to higher stresses in elongation than in shear. For both materials, the steady-state elastic compliances in the nonlinear range decrease with increasing stress in shear as well as in elongation. However, the decrease in elongation is more pronounced.
Keywords: Polypropylene; Polyethylene; Viscosity; Elasticity; Shear; Elongation

Defects caused by degradation - A stumbling block for nanocomposites in thin film capacitors - Werner, Siegfried; Kaschta, Joachim; Schubert, Dirk W. (ICD 2022 - IEEE 2022 4th International Conference on Dielectrics, Proceedings, 2022)
The aim of this study is to shed light on why the often-praised beneficial effects of nanoparticles on dielectric breakdown strength are not observed in biaxially oriented PP-based films. Therefore, thin films of capacitor grade PP and nanocompounds containing one of two SiO2 based nanoparticles (pyrogenic and colloidal) at 2wt.% and 4wt.% were produced at a pilot scale thin film production line. Additionally, neat PP was deliberately degraded to a similar extent using cyclic extrusion on a twin-screw extruder. After cast film extrusion and biaxial stretching using a Karo IV lab stretcher, all films were tested for their dielectric strength, surface roughness, molar mass and particle dispersion using a diamond tip profilometer, HT-GPC and SEM. All films showed a reduction in molar mass of up to 50 % in mathrmM_mathrmw followed by a linear decrease in breakdown strength. It is known that the degradation mechanisms in PP lead to the inclusion of radicals, double bonds and carbonyl groups in the polymer chain, decreasing the width of the bandgap and thereby reducing dielectric strength in a stronger way than nanoparticles could enhance it. This study shows that the negative effect of degradation during processing is probably stronger than the superimposed and potentially beneficial effect of adding nanoparticles.
CRIS-Team Scopus Importer:2022-09-30

Degradation studies of a commercial radiation-resistant polypropylene sterilized by gamma and electron beam technology before and after subsequent accelerated aging cycles - Kremser, Thomas; Susoff, Markus; Roth, Stefan; Kaschta, Joachim; Schubert, Dirk W. (Journal of Applied Polymer Science, 2019)
Irradiation is one of the most widely used technologies for sterilization of medical products. Unfortunately, some polymers in the medical field are susceptible to high-energy radiation. In the case of polypropylene, this leads to yellowing and embrittlement due to degradation mechanisms. This study compares the impact of gamma and eBeam sterilizations at a dose of 45 kGy on a commercially available, radiation-resistant polypropylene in combination with accelerated aging studies. Mechanical behavior as well as yellowing, accompanied by structural investigations like molar mass characterization and crystallinity analysis, have been investigated. It is shown that eBeam has less damaging effects compared with gamma irradiation. This is shown by an initial drop in elongation at break by 46% for gamma irradiated samples in contrast to 24% decrease using eBeam irradiation. Also, an initial drop in molar mass by 43% was found for gamma irradiated samples and by 27% for eBeam. Change in color was observed by an initial increase in the yellowness index of 42% at samples after gamma irradiation, respectively, of 22% for eBeam irradiated samples. Interestingly, molar mass remained constant during aging, whereas yellowing and Embrittlement further change. Additionally, empirical equations were found, which describe the experimental data. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48436.
CRIS-Team Scopus Importer:2019-09-17
Keywords: accelerated aging; degradation; polypropylene; radiation sterilization

Determination of method-invariant activation energies of long-chain branched low-density polyethylenes - Keßner, Ute; Kaschta, Joachim; Münstedt, Helmut (Journal of Rheology, 2009)
The idea to use the temperature dependence of rheological properties, especially the flow activation energy, as a tool to investigate branching structures is well-known from literature. However, there is no common method to obtain activation energies, which are independent of the measuring quantity chosen, particularly, in the case of slightly thermorheologically complex polymers like low-density polyethylene (LDPE). Hence, differing activation energies result, which cannot unequivocally be correlated with the branching structure. This paper describes a method for the determination of method-independent activation energies for thermorheologically complex polymers like LDPE. From a generalized approach to the time-temperature superposition principle, a vertical shift factor is introduced, which is related to the temperature dependence of the linear steady-state compliance. In the case of the complex LDPE, a decrease in the linear steady-state compliance with temperature is found. Taking this experimentally determined shift factor into account leads to activation energies independent of the rheological quantity chosen. These values can be taken to analyze differences of the branching architecture.
Keywords: polymer melts; rheology; viscoelasticity

Determining the coating speed limitations for organic photovoltaic inks - Jakubka, Florian; Heyder, Madeleine; Kaschta, Joachim; Machui, Florian; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2013)
To determine the output capability of present organic photovoltaic (OPV) materials, it is important to know the theoretical maximum coating speeds of the used semiconductor formulations. Here, we present a comprehensive investigation of the coating stability window of several prototype organic semiconductor inks relevant for organic solar cells. The coating stability window was first determined experimentally by a sheet to sheet coater at velocities of up to 10 m/min. A numerical simulation model based on the "Coating Window Suite 2010" software was established to give insight into the coating stability limitations at higher coating velocities. An analysis of PEDOT:PSS [poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)] in a water/isopropyl alcohol mixture as well as P3HT:PCBM [poly(3-hexylthiophene-2,5-diyl):Phenyl-C61-butyric acid methyl ester] in chlorobenzene, o-xylene and tetrahydronaphthalene showed the possibility of coating speeds up to 60 m/min. The simulation further revealed the maximum coating head distances for a given wet film thickness. Finally, we show a solar-cell with slot-die coated PEDOT:PSS and P3HT:PCBM-layer based on the parameters obtained by the simulated data, which exhibits reasonable performance. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: OPV solar cell; Slot-die coating; Coating speed

Differentiating gel compositions of silicone breast implants from Poly Implant Prothèse and other Manufactures - Schubert, Dirk W.; Horch, Raymund E.; Kaschta, Joachim (Book of Abstracts, 2013)

Discrepancies between linear viscoelastic measurements and double-reptation predictions for commercial polystyrene samples - Guzmán, Job D.; Mangnus, Marc; Aerts, Peter; Mes, Edwin; Kaschta, Joachim; Pierini, Pete (Rheologica Acta, 2008)
We have found discrepancies between the predictions of two double-reptation models and the corresponding linear viscoelasticity measurements for commercial, polydisperse polystyrene samples with weight-average molecular weights ranging from 140 to 300kg/mol. The accuracy of the experimental data has been confirmed by conducting viscoelasticity measurements in different laboratories using different types of rheometers and by verifying that small distortions in chromatographic measurements cannot account for the discrepancies seen in the viscoelastic response. In addition, we show that the discrepancies between predictions and measurements are systematic, suggesting that gaps in the theory are responsible for the mismatch. Is it concluded that commercial polystyrene resins may pose additional challenges for rheological modeling because of their relatively high polydispersity and low degree of entanglement. The experimental data given here can be used to validate future modeling effort
Keywords: molecular weight distribution; linear viscoelasticity; double reptation

Eine Geschichte des Versagens - der PIP Skandal - Schubert, Dirk W.; Kaschta, Joachim; Horch, Raymund E.; Walter, Bastian; Daenicke, Jonas; Wichert, Franziska (Würzbuger Tage 2014, 2014)

Eine Geschichte des Versagens - der PIP Skandal - Schubert, Dirk W.; Kaschta, Joachim; Horch, Raymund E.; Walter, Bastian; Daenicke, Jonas; Wichert, Franziska (Würzburger Tage 2014, 2014)

Elongational Flow Properties of Long-Chain Branched Poly(Ethylene Terephthalate) - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Polychar 22nd, 2014)

Elongational Flow Properties Of Long-Chain Branched Poly(Ethylene Terephthalate) - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Entanglement network formed in miscible PLA/PMMA blends and its role in rheological and thermo-mechanical properties of the blends - Hao, Xiaoqiong; Kaschta, Joachim; Liu, Xian Hu; Pan, Yamin; Schubert, Dirk W. (Polymer, 2015)
The miscible amorphous/semi-crystalline polymer blends with shape memory potential has received increasing interests in recent years. In this work, the shape memory mechanism of the miscible amorphous PMMA/semi-crystalline PLA blends was investigated using thermo-mechanical and rheological approaches. With the incorporation of PMMA into PLA, a broad glass transition and increased glass transition temperature Tg were observed by differential scanning calorimetry (DSC) measurements. The broadening of glass transition is attributed to the local nanoscale heterogeneities in the miscible blend system which is related to the self-concentration of the components. The degree of molecular entanglement of the blends was derived based on the oscillatory rheological measurements, showing that the dissimilar chains are more likely to entangle with each other than the similar ones, and the entanglement density ve is enhanced with increased PMMA content up to 50% where a 100% recovery of the initial shape is yielded. After that, ve is reduced with the addition of PMMA. The mechanism underlying the shape memory property is further validated by performing the shape memory test on the PLA/PMMA blend films at respective Tg. It is evident that for the semi-crystalline blends (PLA rich), PLA crystallites and molecular entanglement provide physical cross-links for shape recording, while a negative effect of crystallinity on the shape recovery ratio is obtained due to the strain-induced crystallization and chain slippage between the crystalline and amorphous chains. In contrast, for the amorphous blends (PMMA rich), the shape recovery ratio shows a strong positive linear dependence on ve, and the entanglement network is regard as the most important factor in the shape memory performanc
Keywords: Rheological property; Shape memory polymer; Molecular entanglement

Entanglement network formed in miscible PLA/PMMA blends and its role in rheological and thermo-mechanical properties of the blends - Hao, Xiaoqiong; Kaschta, Joachim; Liu, Xian Hu; Pan, Yamin; Schubert, Dirk W. (Polymer, 2015)
The miscible amorphous/semi-crystalline polymer blends with shape memory potential has received increasing interests in recent years. In this work, the shape memory mechanism of the miscible amorphous PMMA/semi-crystalline PLA blends was investigated using thermo-mechanical and rheological approaches. With the incorporation of PMMA into PLA, a broad glass transition and increased glass transition temperature Tg were observed by differential scanning calorimetry (DSC) measurements. The broadening of glass transition is attributed to the local nanoscale heterogeneities in the miscible blend system which is related to the self-concentration of the components. The degree of molecular entanglement of the blends was derived based on the oscillatory rheological measurements, showing that the dissimilar chains are more likely to entangle with each other than the similar ones, and the entanglement density ve is enhanced with increased PMMA content up to 50% where a 100% recovery of the initial shape is yielded. After that, ve is reduced with the addition of PMMA. The mechanism underlying the shape memory property is further validated by performing the shape memory test on the PLA/PMMA blend films at respective Tg. It is evident that for the semi-crystalline blends (PLA rich), PLA crystallites and molecular entanglement provide physical cross-links for shape recording, while a negative effect of crystallinity on the shape recovery ratio is obtained due to the strain-induced crystallization and chain slippage between the crystalline and amorphous chains. In contrast, for the amorphous blends (PMMA rich), the shape recovery ratio shows a strong positive linear dependence on ve, and the entanglement network is regard as the most important factor in the shape memory performanc
Keywords: Rheological property; Shape memory polymer; Molecular entanglement

Evaluation of fibroblasts adhesion and proliferation on alginate-gelatin crosslinked hydrogel - Sarker, Bapi; Singh, Raminder; Silva, Raquel; Roether, Judith; Kaschta, Joachim; Detsch, Rainer; Schubert, Dirk W.; Cicha, Iwona; Boccaccini, Aldo R. (PLoS ONE, 2014)
Due to the relatively poor cell-material interaction of alginate hydrogel, alginate-gelatin crosslinked (ADA-GEL) hydrogel was synthesized through covalent crosslinking of alginate di-aldehyde (ADA) with gelatin that supported cell attachment, spreading and proliferation. This study highlights the evaluation of the physico-chemical properties of synthesized ADA-GEL hydrogels of different compositions compared to alginate in the form of films. Moreover, in vitro cell-material interaction on ADA-GEL hydrogels of different compositions compared to alginate was investigated by using normal human dermal fibroblasts. Viability, attachment, spreading and proliferation of fibroblasts were significantly increased on ADA-GEL hydrogels compared to alginate. Moreover, in vitro cytocompatibility of ADA-GEL hydrogels was found to be increased with increasing gelatin content. These findings indicate that ADA-GEL hydrogel is a promising material for the biomedical applications in tissue-engineering and regeneration. Copyright:

Evaluation of the diffusion properties of cyclic siloxanes through the silicone breast implant shell - Daenicke, Jonas; Schubert, Dirk W.; Gedde, Ulf; Hedenqvist, Mikael; Linde, Erik; Kaschta, Joachim; Horch, Raymund E. (14th Bayreuth Polymer Symposium, 2015)

Evaluation of the diffusion properties of cyclic siloxanes through the silicone breast implant shell - Daenicke, Jonas; Schubert, Dirk W.; Gedde, Ulf; Hedenqvist, Mikael; Linde, Erik; Kaschta, Joachim; Horch, Raymund E. (Nordic Polymer Days, 2015)

Fabrication and Properties of Injection Moulded Hardmetal Parts by use of a Pressure Die Casting Machine - Raduta, Sorina; Grötzschel, Gerhard; Kaschta, Joachim; Rosiwal, Stefan; Singer, Robert (1998 PM World Congress, 1998)

Fabrication of alginate-gelatin crosslinked hydrogel microcapsules and evaluation of the microstructure and physico-chemical properties - Sarker, Bapi; Papageorgiou, Dimitrios G.; Silva, Raquel; Zehnder, Tobias; Gul-E-Noor, Farhana; Bertmer, Marko; Kaschta, Joachim; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2014)
Microencapsulation of cells by using biodegradable hydrogels offers numerous attractive features for a variety of biomedical applications including tissue engineering. This study highlights the fabrication of microcapsules from an alginate-gelatin crosslinked hydrogel (ADA-GEL) and presents the evaluation of the physico-chemical properties of the new microcapsules which are relevant for designing suitable microcapsules for tissue engineering. Alginate di-aldehyde (ADA) was synthesized by periodate oxidation of alginate which facilitates crosslinking with gelatin through Schiff's base formation between the free amino groups of gelatin and the available aldehyde groups of ADA. Formation of Schiff's base in ADA-GEL and aldehyde groups in ADA was confirmed by FTIR and NMR spectroscopy, respectively. Thermal degradation behavior of films and microcapsules fabricated from alginate, ADA and ADA-GEL was dependent on the hydrogel composition. The gelation time of ADA-GEL was found to decrease with increasing gelatin content. The swelling ratio of ADA-GEL microcapsules of all compositions was significantly decreased, whereas the degradability was found to increase with the increase of gelatin ratio. The surface morphology of the ADA-GEL microcapsules was totally different from that of alginate and ADA microcapsules, observed by SEM. Two different buffer solutions (with and without calcium salt) have an influence on the stability of microcapsules which had a significant effect on the gelatin release profile of ADA-GEL microcapsules in these two buffer solutions. © 2014 The Royal Society of Chemistry.

Failure of Silicone Breast Implants – New Insights by Mapping the Mechanical Properties of Implant Shells - Schubert, Dirk W.; Horch, Raymund E.; Kaschta, Joachim; Daenicke, Jonas; Walter, Bastian (13th Bayreuth Polymer Symposium, 2013)

Failure of Silicone Breast Implants – New Insights by Mapping the Mechanical Properties of Implant Shells - Schubert, Dirk W.; Kaschta, Joachim; Horch, Raymund E.; Walter, Bastian; Daenicke, Jonas (Book of Abstracts, 2013)

Failure of Silicone Breast Implants – Novel Insights by Mapping the Mechanical Properties of Implant Shells - Schubert, Dirk W.; Horch, Raymund E.; Kaschta, Joachim; Daenicke, Jonas; Walter, Bastian (Nordic Polymer Days, 2013)

From trash to treasure in additive manufacturing: Recycling of polymer powders by acid catalyzed hydrolysis - Hesse, Nicolas; Jaksch, Andreas; Kaschta, Joachim; Groh, Dominik; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2023)
A persistent problem in laser powder bed fusion (PBF) additive manufacturing (AM) of polymers is the accumulation of used feedstock material that cannot be reprocessed due to alterations in the physical and chemical structure upon ageing at elevated temperatures. The chemical ageing of polyamide 12, the most frequently used feedstock in PBF of polymers, occurs due to solid-state post-condensation during the AM process and can be reversed by appropriate processing. This paper investigates the application of acid-catalyzed hydrolytic reconditioning to restore virgin powder properties from used and annealed feedstock material, highlighting a pathway to more sustainability in AM. The proposed method is optimized towards PBF-printing relevant properties and mechanical characteristics of parts build with the recycled feedstock material, which are benchmarked against conventional powder refreshing strategies.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Hydrolysis; Polyamide 12; Polymer ageing; Polymer recycling; Powder bed fusion; Powder characterization

Gelation of polyvinylbutyral solutions by the addition of tetrabutyl orthotitanate - Wegener, Carsten Moritz; Kaschta, Joachim; Münstedt, Helmut; Roosen, Andreas (Rheologica Acta, 2014)
This paper discusses the gelation of polyvinylbutyral (PVB) solutions by the addition of tetrabutyl orthotitanate. The addition of around 0.10 vol.% tetrabutyl orthotitanate to an ethanol-based PVB solution already causes a pronounced gelation. For the characterization of this gelation reaction, different rheological measurements are used. The characterization is mainly performed in the linear viscoelastic regime. Time sweeps prove the stability of the samples during the measuring time. Frequency sweeps are used to investigate the state of gelation after different reaction times as well as the dependence of the degree of the gelation on the tetrabutyl orthotitanate concentration. Furthermore, the gelation point is determined by measuring the loss factor tan delta as a function of frequency. A strong influence of water on the degree of gelation is shown; by the addition of different amounts of water, the gelation can be controlled or even avoided. Amplitude sweeps reveal the breakdown of certain network structures at high amplitudes which recover after the strain is lowered.
Keywords: Polyvinylbutyral (PVB); Gelation with titanate; Dynamic mechanical analysis (DMA); Network characterization; Gel point

High precision processing of flexible P3HT/PCBM modules with geometric fill factor over 95% - Kubis, Peter; Lucera, Luca; Machui, Florian; Spyropoulos, Georgios; Cordero, Johann; Frey, Alfred; Kaschta, Joachim; Voigt, Monika; Matt, Gebhard; Zeira, Eitan; Brabec, Christoph (Organic Electronics, 2014)
Flexible OPV modules, based on P3HT:PCBM as absorber layer, were manufactured with a power conversion efficiency over 3% and for a total area of 3500 mm(2) consisting of 14 in series interconnected cells. The modules utilize the excellent mechanical and the outstanding optical properties of sputtered transparent ITO-Metal-ITO (IMI) electrodes deposited on the PET foil on the one hand, and the combination of large area slot-die coating with high resolution ultrafast laser patterning on the other hand. The manufacturing of modules with outstanding performance was found to be reproducible. The right combination of innovative electrodes and smart roll-to-roll compatible processing technologies demonstrates a viable path towards high efficient industrial module technology. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Flexible transparent electrode; Flexible OPV module; Slot-die coating; Ultra-fast laser patterning; High geometric fill factor

High speed determination of the degree of crosslinking of PEX using a rheological test - Falk, M.; Heiduk, I.; Kaschta, Joachim; Schubert, Dirk W. (10th Annual European Rheology Conference, 2015)

High speed determination of the degree of crosslinking of PEX using a rheological test - Heiduk, I.; Falk, M.; Kaschta, Joachim; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Hybrid hydrogels based on keratin and alginate for tissue engineering - Silva, Raquel; Singh, Raminder; Sarker, Bapi; Papageorgiou, Dimitrios G.; Juhasz, Judith A.; Roether, Judith; Cicha, Iwona; Kaschta, Joachim; Schubert, Dirk W.; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2014)
Novel hybrid hydrogels based on alginate and keratin were successfully produced for the first time. The self-assembly properties of keratin, and its ability to mimic the extracellular matrix were combined with the excellent chemical and mechanical stability and biocompatibility of alginate to produce 2D and 3D hybrid hydrogels. These hybrid hydrogels were prepared using two different approaches: sonication, to obtain 2D hydrogels, and a pressure-driven extrusion technique to produce 3D hydrogels. All results indicated that the composition of the hydrogels had a significant effect on their physical properties, and that they can easily be tuned to obtain materials suitable for biological applications. The cell-material interaction was assessed through the use of human umbilical vein endothelial cells, and the results demonstrated that the alginate/keratin hybrid biomaterials supported cell attachment, spreading and proliferation. The results proved that such novel hybrid hydrogels might find applications as scaffolds for soft tissue regeneration. © 2014 the Partner Organisations.

Hydrogel matrices based on elastin and alginate for tissue engineering applications - Silva, Raquel; Singh, Raminder; Sarker, Bapi; Papageorgiou, Dimitrios G.; Juhasz-Bortuzzo, Judith A.; Roether, Judith; Cicha, Iwona; Kaschta, Joachim; Schubert, Dirk W.; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2018)
Hydrogels from natural polymers are widely used in tissue engineering due to their unique properties, especially when regarding the cell environment and their morphological similarity to the extracellular matrix (ECM) of native tissues. In this study, we describe the production and characterization of novel hybrid hydrogels composed of alginate blended with elastin from bovine neck ligament. The properties of elastin as a component of the native ECM were combined with the excellent chemical and mechanical stability as well as biocompatibility of alginate to produce two hybrid hydrogels geometries, namely 2D films obtained using sonication treatment and 3D microcapsules produced by pressure-driven extrusion. The resulting blend hydrogels were submitted to an extensive physico-chemical characterization. Furthermore, the biological compatibility of these materials was assessed using normal human dermal fibroblasts, indicating the suitability of this blend for soft tissue engineering. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Alginate; Elastin; Hybrid hydrogels; Soft matrices; Tissue engineering

Improving alginate printability for biofabrication: establishment of a universal and homogeneous pre-crosslinking technique - Hazur, Jonas; Detsch, Rainer; Karakaya, Emine; Kaschta, Joachim; Teßmar, Jörg; Schneidereit, Dominik; Friedrich, Oliver; Schubert, Dirk W.; Boccaccini, Aldo R. (Biofabrication, 2020)
Many different biofabrication approaches as well as a variety of bioinks have been developed by researchers working in the field of tissue engineering. A main challenge for bioinks often remains the difficulty to achieve shape fidelity after printing. In order to overcome this issue, a homogeneous pre-crosslinking technique, which is universally applicable to all alginate-based materials, was developed. In this study, the Young's Modulus after post-crosslinking of selected hydrogels, as well as the chemical characterization of alginate in terms of M/G ratio and molecular weight, were determined. With our technique it was possible to markedly enhance the printability of a 2% (w/v) alginate solution, without using a higher polymer content, fillers or support structures. 3D porous scaffolds with a height of around 5 mm were printed. Furthermore, the rheological behavior of different pre-crosslinking degrees was studied. Shear forces on cells as well as the flow profile of the bioink inside the printing nozzle during the process were estimated. A high cell viability of printed NIH/3T3 cells embedded in the novel bioink of more than 85% over a time period of two weeks could be observed.
CRIS-Team Scopus Importer:2020-07-24
Keywords: alginate; bioink; bioprinting; pre-crosslinking; printability; rheology; shape fidelity

Influence of molar mass distribution and long-chain branching on strain hardening of low density polyethylene - Stadler, Florian; Kaschta, Joachim; Münstedt, Helmut; Becker, Florian; Buback, Michael (Rheologica Acta, 2009)
Low-density polyethylenes (LDPE) were synthesized in a laboratory-scale autoclave under high pressure. These samples were found to possess a high molar mass tail, resulting in a distinctly bimodal molar mass distribution and a lower concentration of long-chain branching than typical of commercial LDPEs. Rheological experiments in elongation showed that these samples exhibit a very pronounced strain hardening, which could be favorable for distinct processing operations. Although the samples have a rather high molar mass (M(w) = 2...4 x 10(6) g/mol), their zero shear-rate viscosities eta(0) and their shear thinning behavior are still in a range, where thermoplastic processing is possible. Aqualitative understanding of the experimental results is tried by the model of the Cayley tree.
Keywords: Low-density polyethylene; Autoclave process; Molar mass distribution; Long-chain branching; Elongational rheology; Viscosity functions

Influence of molecular parameters on the stress dependence of viscous and elastic properties of polypropylene melts in shear - Resch, Julia; Kaschta, Joachim; Wolff, Friedrich; Münstedt, Helmut (Rheologica Acta, 2011)
The stress dependencies of the steady-state viscosity eta and, particularly, that of the steady-state elastic compliance J(e) of various linear isotactic polypropylenes (PP) and one long-chain branched PP are investigated using creep-recovery tests. The creep stresses applied range from 2 to 10,000 Pa. In order to discuss the stress-dependent viscosity eta and elastic compliance J(e) with respect to the influence of the weight average molar mass M-w and the polydispersity factor M-w/M-n the PP are characterized by SEC-MALLS. For the linear PP, linear steady-state elastic compliances J(e)(0) in the range of 10(-5)-10(-3) Pa-1 are obtained depending on the molar mass distribution. J(e)(0) of the LCB-PP is distinctly higher and comes to lie at around 10(-2) Pa-1. J(e)(0) is found to be independent of M-w but strongly dependent on polydispersity. eta and J(e) decrease with increasing stress. For the linear PP, J(e) as a function of the stress tau is temperature independent. The higher M-w/M-n the stronger is the shear thinning of eta and the more pronounced is the stress dependence of J(e). For the LCB-PP, the strongest stress dependence of eta and J(e) is observed. Furthermore, for all PP J(e) reacts more sensitively to an increasing stress than eta. A qualitative explanation for the stronger stress dependence of J(e) compared to eta is given by analyzing the contribution of long relaxation times to the viscosity and elasticity.
Keywords: Polypropylene; Viscosity; Steady-state elastic compliance; Stress dependence; Molecular structure

Influence of temperature and stretching speed on the homogeneity of biaxial oriented polypropylene films from binary and ternary blends - Seidl, Stephan; Kaschta, Joachim; Schubert, Dirk W. (13th Bayreuth Polymer Symposium, 2013)

Influence of Temperature and Stretching Speed on the Homogeneity of Biaxial Oriented Polypropylene Films From Binary and Ternary Blends - Seidl, Stephan; Kaschta, Joachim; Schubert, Dirk W. (Book of Abstracts, 2013)

Influence of various pretreatments on molecular and rheological properties of a linear and a long-chain branched polypropylene - Münstedt, Helmut; Kaschta, Joachim (Rheologica Acta, 2024)
The influence of a mechanical or a thermal pretreatment of a linear (L-PP) and a long-chain branched polypropylene (LCB-PP) in the molten state was studied. The molar mass distributions and the branching structure were determined by high-temperature gel permeation chromatography HT-GPC coupled with laser-light scattering. The samples were extruded through long or short capillaries of various geometries corresponding to a predominant shear or elongational deformation. As a rheological probe, the extrudate swell at low stresses was measured for the differently pretreated samples. For the L-PP, neither molecular nor rheological changes were observed. However, the extrudate swell of the LCB-PP was found to decrease with increasing volume throughput. It was more strongly affected by shear in the capillary than by molecule stretching in the entry region. The smaller extrudate swell was accompanied by a decrease of the high molar mass tail of the LCB-PP, which could be the reason for the decay of swell, in principle. However, a comparable degradation of the high molar mass tail was obtained by a pure thermal treatment that was shown to leave the extrudate swell unchanged. This result and the unaffected branching structures found by high-temperature gel permeation chromatography (HT-GPC) support the hypothesis of a change of the branching topography by the mechanical pretreatment.<br

Intermolecular cooperativity and entanglement network in a miscible PLA/PMMA blend in the presence of nanosilica - Hao, Xiaoqiong; Kaschta, Joachim; Pan, Yamin; Liu, Xian Hu; Schubert, Dirk W. (Polymer, 2016)
Nanosilica filled polylactide (PLA)/Poly(methyl methacrylate) (PMMA) 50/50 blends with varying silica concentrations were prepared by melt mixing. In this work, the effects of silica concentration and the preferential adsorption between silica and the component on the thermo-mechanical and rheological properties of PLA/PMMA blends were systematically investigated. The results of DSC indicate the miscibility of PLA/PMMA/silica nanocomposites in the solid state, and the incorporation of nanosilica does not only increase the glass transition temperature but also extend the broadness of glass transition. Local nanoscale heterogeneities in the miscible blends are proposed due to the self-concentration of the components, and the presence of nanosilica increased the concentration fluctuation and dynamic heterogeneity of the PLA/PMMA blends. A distinct "crater" structure can be observed in the fractured surfaces of the blend nanocomposites. According to the results of SEM and rheological measurements, it was proposed that PLA molecules were selectively adsorbed on the surface of nanosilica, and the preferential adsorption of PLA changed the blend composition in the "crater" structure and the bulk matrix. The phase separation temperature of the filled PLA/PMMA blends was also improved by the incorporation of nanosilica, implying a potential role of nanosilica in improving the phase stability of PLA/PMMA blends. In addition, nanosilica could increase and entanglement density and decrease the entanglement molar mass of the blends in a concentration-dependent manner. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Miscible blend; Nanocomposite; Preferential adsorption

Investigation and characterization of the additive manufacturing of polycaprolactone/bioactive glass hybrid scaffolds for bone tissue engineering via material extrusion processing - Gritsch, Lukas; Askanian, Haroutioun; Bednarzig, Vera; Schrüfer, Stefan; Kaschta, Joachim; Blavignac, Christelle; Peuble, Steve; Gallice, Frederic; Jallot, Edouard; Boccaccini, Aldo R.; Lao, Jonathan (Progress in Additive Manufacturing, 2023)
Thanks to its versatility and effectiveness, additive manufacturing is expected to completely revolutionize the biomedical science field. In bone regenerative medicine, in particular, additive manufacturing has the great potential of opening new avenues of development for patient-specific ad hoc therapies. In theory, a defect could be scanned and precisely replicated, thus offering the best fitting for each patient. The main bottleneck to date is the relatively scarce availability of materials that can be printed reliably and consistently. This is the case for organic/inorganic hybrids, materials produced by sol–gel chemistry that combine the advantages of polymers and bioinorganics at the molecular scale. Due to their complex structure and unique rheological and mechanical properties, the printing of hybrids remains challenging. With this study, we aim to investigate the rheological, thermal and molecular properties of a class I polycaprolactone/bioactive glass hybrid and discover how they correlate with the printability of the material. The molecular weight distribution (gel permeation chromatography), thermal properties (thermal gravimetric analysis, differential scanning calorimetry) and rheological properties of each hybrid material were investigated at all stages of processing. Printing trials via direct material extrusion processing followed by morphological characterization were performed on both polymers and hybrids. Their apatite-forming ability in simulated body fluid was evaluated by scanning electron microscopy and particle-induced X-ray emission. Results confirmed the successful manufacturing of organic/inorganic hybrids using direct material extrusion processing for the first time. Three-dimensional scaffolds were successfully produced without the need for further processing. No additional solvents or convoluted indirect approaches were necessary. Thanks to the thermal analysis, an ideal temperature window for printing was identified. SBF immersion assays confirmed that the material's bioactivity is retained after printing. Considering the presented findings, material extrusion processing might develop into an essential technique for fabricating superior 3D bioactive scaffolds for bone tissue engineering. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-09-29
Keywords: Additive manufacturing; Bioactive glasses; Bioactivity; Fused deposition modeling; Hybrids; Polycaprolactone

Is short term intraoperative application of disinfectants harmful to breast implants in breast reconstruction? An experimental study and literature survey - Schmitz, Marweh; Schubert, Dirk W.; Kaschta, Joachim; Daenicke, Jonas; Walter, Bastian; Horch, Raymund E. (Journal of the Mechanical Behavior of Biomedical Materials, 2019)
Objectives: Bacterial contamination of breast implants and biofilm formation has been discussed as a major reason for implant loss and capsular contraction. Intra- and perioperative treatment of breast implants with disinfectants to prevent bacterial contamination has been frequently reported. Given the increasing awareness of concerns about product liability the question of whether short-time irrigation of implants with antimicrobial substances during the operative procedure would potentially alter the integrity of the implant shell has attracted legal and medical interest. In this study we therefore investigated whether irrigating breast implants with antimicrobials commonly used in clinical practice with a clinically relevant application time would affect the physical integrity of the implant shell.
CRIS-Team WoS Importer:2019-02-21

Kriech- und Kriecherholungsmessungen zur Charakterisierung von Materialien mit langer charakteristischer Zeit - Walter, Bastian; Kaschta, Joachim (Geesthachter Polymertage: Rheologie von Polymeren für Forschung und Anwendung, 2016)

Lamination and sintering behavior of tape cast, transparent Mg-Al-spinel ceramics - Beck, M.; Hattori, K.; Kaschta, Joachim; Kakimoto, K.; Roosen, A. (Ceramics International, 2015)
High purity Mg–Al–spinel powders were processed to form slurries for tape casting. The dried green tapes were cut and laminated via thermo-compression under uniaxial and isostatic pressure conditions. Finally the laminates were sintered pressurelessly in air. The influence of the transformation temperature of the green tape׳s binder–plasticizer system and of lamination parameters on density and microstructure of the sintered laminates was analyzed. UV‐VIS transmission spectroscopy was performed to measure the transparency of the fired laminates. The interrelation between the lamination parameters, sintering behavior and properties of the sintered product is discussed. Isostatic thermal lamination resulted in higher sintered densities than uniaxial lamination. For both techniques an increase in lamination pressure or temperature led to higher relative densities after sintering. The laminates exhibited total forward transmission values of up to 67% at a wavelength of 700
Keywords: A. Tape casting; Laminated ceramics; D. Spinel; Translucent ceramics

LCB formation in PLA by reactive extrusion - Kaschta, Joachim; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Long-chain branched PLA for biaxially streched film - Kaschta, Joachim; Lanzl, Lydia; Lemppenau, Simon; Schubert, Dirk W. (Abstracts, 2016)

Long-chain branched polylactide by reactive extrusion using a multi-functional chain extender - Kaschta, Joachim; Lanzl, Lydia; Schubert, Dirk W. (Book of Abstracts, 2016)

Long-Chain Branches in Syndiotactic Polypropene Induced by Vinyl Chloride - Stadler, Florian; Arikan, Burçak; Kaschta, Joachim; Kaminsky, Walter (Macromolecular Chemistry and Physics, 2010)
Syndiotactic polypropene was synthesized using a metallocene catalyst system and traces of VC. The use of VC was found to decrease the molar mass (M) over bar (w) of the samples distinctly and linearly, while retaining the molar mass distribution, the crystallinity, and the syndiotacticity. The VC, however, initiates the formation of long-chain branches, which were detected by GPC-MALLS and rheology. Besides their effect on the viscosity and modulus functions, a thermorheologic complexity can be observed. Also the flow activation energy E(a) was found to be increased. The modified samples did not obey the eta(0)/(M) over bar (w) relation for linear sPP, indicating the presence of LCBs.
Keywords: GPC-MALLS; long-chain branches; metallocene catalysts; rheology; syndiotactic polypropene

Magneto-Rheological fluids and elastomers based on injection moldable liquid silicone - Kaschta, Joachim; Musialek, Matthias; Böse, Holger; Schubert, Dirk W. (Book of Abstracts, 2011)

Magneto-rheological Fluids and Elastomers Based on Injection Moldable Liquid Silicone - Kaschta, Joachim; Musialek, Matthias; Böse, Holger; Schubert, Dirk W. (Final Program and Book of Abstract, 2011)

Magneto-Sensitive Elastomers: An Experimental Point of View - Walter, Bastian; Saxena, Prashant; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (85th Annual Meeting of the International Association of Applied Mathematics and Mechanics, 2014)

'Make it Stick' -Influence of Hydrophobicity of Nano Silica Functionalization on Dispersion and Breakdown Performance in BOPP Nanocomposites - Werner, Siegfried; Kellner, Michael; Kaschta, Joachim; Schubert, Dirk W. (Proceedings of the 2024 IEEE 5th International Conference on Dielectrics, ICD 2024, 2024)
This paper aims to evaluate commercial silica nanoparticles with surface functionalization of different hydrophobicity for BOPP capacitor films using a small-scale production process requiring only a few grams of particles. Therefore, capacitor grade PP and 0.5 wt.% of fumed silica were compounded in a laboratory mixer, hot pressed into plugs and biaxially oriented on a laboratory stretching device. Three commercial particle systems with comparable specific surface area but different surface functionalization (methacrylate silane (MAS), octamethylcyclotetrasiloxane (OMCTS) or dimethyldichlorosilane (DDS)) as well as unfunctionalized silica were investigated. Optical microscopy and scanning electron microscopy showed that dispersion improved greatly with higher hydrophobicity. Interestingly, short-term dielectric strength for OMCTS functionalization was 37 V/μm higher than for the PP reference and 34 V/μm higher than for DDS, although both consisted of the same chemical groups. Long-term voltage endurance was improved for the polar MAS functionalization despite the short-term performance being governed by agglomerates. Therefore, a combination of hydrophobic and hydrophilic groups seems promising.
CRIS-Team Scopus Importer:2024-09-06
Keywords: BOPP; dielectric strength; dispersion; nanocomposite; surface functionalization; voltage endurance

Molar Mass and Molecular Weight Distribution Determination Of UHMWPE Synthesized Using a Living Homogeneous Catalyst - Saeid, Talebi; Rob, Duchateau; Sanjay, Rastogi; Peters, Gerrit; Kaschta, Joachim; Peters, Gerrit W. M.; Lemstra, Piet J. (Macromolecules, 2010)
Understanding of the physical characteristics of a polymer requires molar mass determination. For the commercially available polymers, having average molar mass below 1000000 g/mol, chromatography is the method that is often applied to determine the molar mass and molar mass distribution. However, the application of conventional chromatography techniques for polymers having molar mass > 1000 000 g/mol becomes very challenging, and often the results are disputed. In this article, melt rheometry based on the "modulus model" is utilized to measure the molar mass and polydispersity of ultra high-molecular-weight polyethylenes (UHMWPEs) having molar mass > 1000 000 g/mol. Results are compared with the chromatography data of the same polymer samples and the boundary conditions where the chromatography technique fails, whereas the rheometry provides the desired information is discussed. The rheological method is based on converting the relaxation spectrum from the time domain to the molecular weight domain and then Using a regularized integral inversion to recover the molecular weight distribution curve. The method is of relevance in determining very high molar masses (exceeding 3000000 g/mol) that cannot be ascertained conclusively with the existing chromatography techniques. For this study, UHMWPEs with various weight-average molar masses, where the number-average molar mass exceeds > 1000000 g/mol, are synthesized. Catalyst used for the synthesis is a living homogeneous catalyst system: MAO-activated bis(phenoxy imine) titanium dichloride. The rheological behavior of the thus synthesized nascent reactor powders confirms the disentangled state of the polymer that tends to entangle with time in mel

Molecular and Rheological Properties of Peroxide Modified LDPE Based Wood Plastic Composites - Kaschta, Joachim; Harnnarongchai, Wanlop; Schubert, Dirk W. (6th International Symposium on the Separation and Characterization of Natural and Synthetic Macromolecules, 2013)

Molecular structure and rheological properties of a poly(ethylene terephthalate) modified by two different chain extenders - Härth, Michael; Dörnhöfer, Andrea; Kaschta, Joachim; Münstedt, Helmut; Schubert, Dirk W. (Journal of Applied Polymer Science, 2020)
This paper compares the molecular structure and rheological properties of a commercial poly(ethylene terephthalate) (PET) after reactive processing with different concentrations of either pyromellitic dianhydride (PMDA) or a multifunctional epoxide (Joncryl®ADR‐4368) as a chain extender. By size exclusion chromatography with triple detection, an increase of molar mass, a broadening of molar mass distribution, and the generation of long‐chain branched molecules were found for both chain extenders. While gel‐free materials were obtained with PMDA, the processing with Joncryl leads to the formation of gels. The effect of branching, indicated by the Mark–Houwink exponent, is more pronounced for materials with Joncryl compared to PMDA and points to a more compact branching structure of the PET/Joncryl molecules. Rheological measurements in shear and elongation support the analysis from SEC and reveal a complex tree‐like branching structure for both chain extenders. In addition, the role of the two modifiers with respect to processing was assessed.<br

Morphology development, melt linear viscoelastic properties and crystallinity of polylactide/polyethylene/organoclay blend nanocomposites - Abdolrasouli, Medi Haji; Nazockdast, Hossein; Sadeghi, Gity Mir Mohamad; Kaschta, Joachim (Journal of Applied Polymer Science, 2015)
Polylactide/polyethylene blends (PLA/PE) and their nanocomposites were prepared via the melt blending process. The effects of organoclay, compatibilizer (PE‐g‐MA), and PE content on morphology, linear viscoelastic properties of the melt and cold crystallization of the samples have been studied. The Palierne model is applied to predict the rheological behavior of unfilled blends. It implies that there is a quantitative agreement between model and experimental data for low PE content blend. From WAXD and the rheological behavior, it is shown that organoclay exhibits a higher extent of intercalation and dispersion in PLA/PE/organoclay nanocomposite than in PLA/organoclay nanocomposite. The DSC results present that the addition of compatibilizer into blend nanocomposite increases cold crystallization temperature of PLA by about 3°C. This can be explained by the role of compatibilizer in transfer of a part of organoclay from PLA matrix to droplets resulting in increase of PLA chain mobility and, therefore, slightly greater cold crystallization temperature.
Keywords: Clay; Morphology; Crystallization; Rheology

Neuartige Studien zu Silikon-Brustimplantaten - Walter, Bastian; Daenicke, Jonas; Horch, Raymund E.; Kaschta, Joachim; Schubert, Dirk W. (Würzburger Tage 2012, 2014)

Nonlinear viscoelastic behavior or measuring artifact? On the wall slip of magnetorheological (MR) elastomers - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (17th International Congress on Rheology, 2016)

Nonlinear viscoelastic behavior or measuring artifact? On the wall slip of magneto-sensitive elastomers - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (10th Annual European Rheology Conference, 2015)

Novel method to measure surface crystallinity of fibers and nonwovens - Lanyi, Franz; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W. (54th Nordic Polymer Days, 2017)

Novel poly(hydroxyalkanoates)-based composites containing Bioglass® and calcium sulfate for bone tissue engineering - García-García, Jose; Garrido, Leoncio; Quijada-Garrido, Isabel; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Biomedical Materials, 2012)
Three different poly(hydroxyalkanoates) (PHAs), copolymers of poly(3-hydroxybutyrate) (P3HB), have been used to make composites using two different fillers, bioactive glass (type 45S5 Bioglass®) and calcium sulfate dihydrate. The PHAs used were poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [PHBHV] and two copolymers of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [PHBHHx]. The aim of the study was the fabrication and characterization of the new composites and the assessment of the influence of the particular filler combination on the physical properties and bioactivity of the films. The thermal behaviour was studied using differential scanning calorimetry while mechanical properties were evaluated using dynamic mechanic thermal analysis and tensile strength test. The mechanical and thermal properties were affected by particles addition. The distribution of the particles in the polymer matrix, observed by scanning electron microscopy, was directly related to the mechanical properties. The surface characteristics were investigated by contact angle measurements and Raman spectroscopy. The extent of formation of hydroxyapatite (HA) upon immersion in simulated body fluid (SBF) depended on the polymer used, the amount of fillers employed and the time of immersion in SBF. Bioactivity was enhanced in the composites with a rise of hydrophilicity. The HA formation was controllable with time in the case of PHBHHx composites.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.novelp

Novel poly(hydroxyalkanoates)-based composites containing Bioglass (R) and calcium sulfate for bone tissue engineering - García-García, Jose; Garrido, Leoncio; Quijada-Garrido, Isabel; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Biomedical Materials, 2012)
Three different poly(hydroxyalkanoates) (PHAs), copolymers of poly(3-hydroxybutyrate) (P3HB), have been used to make composites using two different fillers, bioactive glass (type 45S5 Bioglass (R)) and calcium sulfate dihydrate. The PHAs used were poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [PHBHV] and two copolymers of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [PHBHHx]. The aim of the study was the fabrication and characterization of the new composites and the assessment of the influence of the particular filler combination on the physical properties and bioactivity of the films. The thermal behaviour was studied using differential scanning calorimetry while mechanical properties were evaluated using dynamic mechanic thermal analysis and tensile strength test. The mechanical and thermal properties were affected by particles addition. The distribution of the particles in the polymer matrix, observed by scanning electron microscopy, was directly related to the mechanical properties. The surface characteristics were investigated by contact angle measurements and Raman spectroscopy. The extent of formation of hydroxyapatite (HA) upon immersion in simulated body fluid (SBF) depended on the polymer used, the amount of fillers employed and the time of immersion in SBF. Bioactivity was enhanced in the composites with a rise of hydrophilicity. The HA formation was controllable with time in the case of PHBHHx composites.

On the Determination of the Enthalpy of Fusion of α-Crystalline Isotactic Polypropylene Using Differential Scanning Calorimetry, X-Ray Diffraction, and Fourier-Transform Infrared Spectroscopy: An Old Story Revisited - Lanyi, Franz; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W. (Advanced Engineering Materials, 2019)
The crystallinity determination of polymers using differential scanning calorimetry (DSC) is a standard procedure in industrial and university research. Its value strongly depends on the enthalpy of fusion, which cannot be determined directly using DSC, but must be calibrated using external methods such as X-ray diffraction (XRD) or density measurements. In addition, the determination of the enthalpy or heat of fusion is not trivial and thus error-prone; hence, values from 60 to 260 J g−1 are quoted for polypropylene in the literature. It is therefore of great relevance to devise a consistent method to determine the heat of fusion. To determine the heat of fusion for polypropylene, a sample set with a broad range of crystallinities is produced using cooling rates between 1 and ≈3500 K min−1. The melting enthalpy of the samples is determined using DSC measurements. The determination of the melting enthalpy based on XRD measurements is discussed in detail, validated using Fourier-transform infrared spectroscopy (FTIR), and compared with values quoted in the open literature. Although two different approaches are used to determine the enthalpy of fusion, a value of 170 ± 3 J g−1 is determined.
CRIS-Team Scopus Importer:2019-11-19
Keywords: differential scanning calorimetry; Fourier-transform infrared spectroscopy; heat of fusion; polypropylenes; X-ray diffraction

On the failure of silicone breast implants: New insights by mapping the mechanical properties of implant shells - Schubert, Dirk W.; Kaschta, Joachim; Horch, Raymund E.; Walter, Bastian; Daenicke, Jonas (Polymer International, 2014)
This review summarizes the knowledge on rupture (in vivo as well as under laboratory conditions) of gel-filled silicone breast implants, which has been an open question since the first implantation in 1962. We present recent progress which has been made by a mapping of the mechanical properties of the shell material together with a statistical failure analysis by means of a Weibull fit. Reference implants and intact as well as ruptured explants are tested after several years in vivo using tensile tests. Up to 110 dumbbell-shaped specimens per implant are measured allowing a detailed mapping of the mechanical properties of the silicone shell. Therefore, it is possible to illustrate the results of the tensile tests by mapping the measured values of the implants in the form of a contour plot revealing novel insights. The contour plots clearly display that the mechanical behaviour (e.g. stress at break) varies significantly over the shell. Additionally, a map is proposed which clearly shows separated clusters for different manufacturers and product categories. © 2013 Society of Chemical Industry
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-TM.onthef

On the Preparation, Characterisation, Modelling and Simulation of Magneto-Sensitive Elastomers - Walter, Bastian; Saxena, Prashant; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (Proceedings of the Second Seminar on the Mechanics of Multifunctional Materials, 2014)
UnivIS-Import:2015-07-08:Pub.2014.tech.FT.FT-TM.onthep

On the Preparation, Characterization, Modeling and Simulation of Magneto-Sensitive Elastomers - Walter, Bastian; Saxena, Prashant; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (14th International Conference on Electrorheological Fluids and Magnetorheological Suspensions, 2014)

On the wall slip of magnetorheological elastomers in parallel-plate rotational rheometry - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (7th ECCOMAS Thematic Conference on Smart Structures and Materials, 2015)

On the wall slip phenomenon of elastomers in oscillatory shear measurements using parallel-plate rotational rheometry: I. Detecting wall slip - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (Polymer Testing, 2017)
A systematic study is presented in order to reveal the occurrence of wall slip of pre-prepared elastomeric samples characterized with the use of rotational rheometry. To exclude effects that could be attributed to additional functional fillers, both an unfilled (primarily used) and lightly silica reinforced (complementary system) silicone rubber are evaluated. Cylindrical samples are prepared by casting using a standardized methodology and examined by means of a stress-controlled parallel-plate rotational rheometer. As a control test, samples are also cured within the rheometer (in situ), thereby fixing them to the measuring plates and firmly establishing their response in “no-slip” conditions. The experiments suggest that wall slip, postulated to be caused by an adhesive failure at the sample-plate interface, may occur if the deformation is sufficiently large and no cohesive failure is present. It is detected by an increase in the loss modulus that is related to the adhesive failure associated with local dynamic friction, resulting in increased dissipated energy. Direct (via raw waveform data and normalized Lissajous figures) and indirect (via fast-Fourier-transformation) analysis of the overall system response for a single steady state deformation cycle provided further insights into the mechanism of wall slip.
Keywords: Wall slip; Adhesive failure; Measuring artifact; Large amplitude oscillatory shear; Silicone rubber; Parallel-plate rotational rheometry

On the wall slip phenomenon of elastomers in oscillatory shear measurements using parallel-plate rotational rheometry: II. Influence of experimental conditions - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (Polymer Testing, 2017)
The use of parallel-plate rotational rheometry to characterize ex situ pre-prepared samples of rubber-like polymers is motivated by, for example, the investigation of magneto-rheological elastomers. When exceeding a critical excitation amplitude in oscillatory shear experiments, these elastomeric samples are prone to slip at the sample-plate contact interface. This phenomenon, known as wall slip, starts to occur at the sample's outer rim and leads to an imperfect force transfer onto the sample. This results in a systematic error of measured rheological material quantities. A thorough investigation is presented to reveal how this phenomenon is affected by selected experimental conditions, namely the static axial preload and measuring frequency. For this purpose disc-shaped samples composed of an unfilled silicone rubber are prepared by casting and examined by means +of a controlled stress rotational rheometer equipped with a serrated rotor configuration. The oscillatory strain sweep experiments suggest that wall slip, exclusively present at the serrated rotor surface, is significantly influenced by the static preload. In contrast, only a slight frequency dependence is observed within the examined experimental conditions. Further insights into the wall slip mechanism were attained by two novel methodologies. It is shown that it is possible to produce a master curve for the various applied preloads. This demonstrates that the physical mechanism behind wall slip is independent of the axial force. Furthermore, we derive an empirical model for the criterion governing the onset of wall slip. This links the critical stress at which wall slip is initiated to the static friction condition and geometrical aspects of the rotor configuration. From this it is anticipated that the conditions for reliable experiments involving ex situ pre-prepared samples composed of low damping elastomers can, in the future, be estimated a priori</em
Keywords: Wall slip; Adhesive failure; Measuring artifact; Large amplitude oscillatory shea; Silicone rubber; Parallel-plate rotational rheometry

Poly(butylene terephthalate) for Laser Powder Bed Fusion of Polymers: Feedstock Precipitation and Powder Characterization - Tischer, Florentin; Düsenberg, Björn; Kaschta, Joachim; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (ACS Applied Polymer Materials, 2024)
Powder bed fusion of polymers with a laser beam (PBF-LB/P) is a layer-based additive manufacturing method that excels in producing functional components of complex geometries. However, the limitation of commercially available materials to mostly polyamides reduces the range of applications for PBF-LB/P-processed parts. Recently, liquid−liquid phase separation and crystallization have been reported as a suitable method to produce poly(butylene terephthalate) (PBT) microparticles of good flowability as a PBF-LB/P feedstock. PBT is an interesting plastic feedstock as its properties allow for an extension of the application of AM-built parts in the automotive and electronics sectors. Starting from PBT feed materials with different molar mass distributions, we investigate the effect of the feed material used in the thermal precipitation process under otherwise identical process parameters on the resulting PBT powder properties. The thermal precipitation process is highly robust with respect to bulk solid properties, such as particle size distribution, particle shape, flowability, and intrinsic properties (crystal structure and melting behavior). These product characteristics are virtually unaffected by the average molar mass of the PBT feed. Melt crystallization is accelerated, while the viscosity decreases with decreasing molecular mass. Once favorable process conditions are defined, which lead to powders with suitable properties, the crystallization kinetics and melt viscosity can be adjusted accordingly without changing the powder properties. Key parameters, which influence part porosity (through melt coalescence), layer adhesion, or the tendency of the material to warp during the PBF-LB/P process, are adjustable to produce a customized starting materia
Keywords: powder characterization; powder production; poly(butylene terephthalate); powder bed fusion; liquid−liquid phase separation

Polylactide/organoclay nanocomposites: The effect of organoclay types on the structure development and the kinetic of cold crystallization - Abdolrsaouli, Mehdi Haji; Babaei, Amir; Kaschta, Joachim; Nazockdat, Hossein (Journal of Vinyl & Additive Technology, 2019)
Polylactide (PLA)/organoclay composites were prepared by melt compounding with 4 phr of two different types of organoclays (cloisite 20A and cloisite 30B). Structure development and nonisothermal kinetic of cold crystallization of PLA/organoclay nanocomposites were examined by using of X-ray diffraction technique, transmission electron microscopy, melt viscoelastic measurements, and differential scanning calorimetry. XRD results demonstrated that the melt intercalation of PLA chains into the cloisite 30B and cloisite 20A galleries was achieved to the same extent. However, it was shown that, PLA/cloisite 20A sample exhibited a significant viscosity upturn and a pronounced nonterminal low frequency storage modulus whose values were greater than those of PLA/cloisite 30B nanocomposite. A detailed analysis of the linear melt viscoelastic properties for the filled and unfilled samples at low frequencies was conducted by fitting the complex viscosity and storage modulus data with Carreau-Yasuda and Fractional Zener models, respectively. The glass transition, cold crystallization, melting temperature, and degree of crystallinity of virgin PLA and PLA/organoclay nanocomposites were inspected. Subsequently, the cold crystallization kinetics was analyzed by Avrami, Jezioney, and Lauritzen-Hoffman kinetic models. It was shown that, the crystallization rate followed Avrami equation with the exponent n around 2.4. From Lauritzen-Hoffman equation and Kissinger model, the nucleation parameter K-g and activation energy were estimated, respectively. J. VINYL ADDIT. TECHNOL., 25:48-58, 2019. (c) 2018 Society of Plastics Engineers
CRIS-Team WoS Importer:2019-02-21

Polymer-functionalised nanograins of Mg-doped amorphous calcium carbonate via a flow-chemistry approach - Demmert, Benedikt; Schinzel, Frank; Schüßler, Martina; Mondeshki, Mihail; Kaschta, Joachim; Schubert, Dirk W.; Jacob, Dorrit E.; Wolf, Stephan (Materials, 2019)
Calcareous biominerals typically feature a hybrid nanogranular structure consisting of calcium carbonate nanograins coated with organic matrices. This nanogranular organisation has a beneficial effect on the functionality of these bioceramics. In this feasibility study, we successfully employed a flow-chemistry approach to precipitate Mg-doped amorphous calcium carbonate particles functionalized by negatively charged polyelectrolytes-either polyacrylates (PAA) or polystyrene sulfonate (PSS).We demonstrate that the rate of Mg incorporation and, thus, the ratio of the Mg dopant to calcium in the precipitated amorphous calcium carbonate (ACC), is flow rate dependent. In the case of the PAA-functionalized Mg-doped ACC, we further observed a weak flow rate dependence concerning the hydration state of the precipitate, which we attribute to incorporated PAA acting as a water sorbent; a behaviour which is not present in experiments with PSS and without a polymer. Thus, polymer-dependent phenomena can affect flow-chemistry approaches, that is, in syntheses of functionally graded materials by layer-deposition processes.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Amorphous calcium carbonate; Biomaterials; Flow-chemistry; Microfluidics; Nanoceramics

Prediction of steady-state viscous and elastic properties of polyolefin melts in shear and elongation - Rolón-Garrido, Víctor; Resch, Julia; Wolff, Friedrich; Kaschta, Joachim; Münstedt, Helmut; Wagner, Manfred (Rheologica Acta, 2011)
The linear and nonlinear steady-state viscosities and elastic compliances were measured in shear and elongational flows for two low-density polyethylenes, a linear polypropylene, and two metallocene catalyzed polyethylenes (one linear and one long-chain branched) by Wolff et al. (Rheol Acta 49:95-103, 2010) and Resch (dissertation, 2010). Comprehensive data of this type are rarely found in the literature, and comprehensive modeling of both viscous and elastic effects is even rarer. In this contribution, the reliability of a modeling approach proposed by Laun (J Rheol 30(3):459-501, 1986) and based on the damping function concept is tested. The strain hardening seen for the long-chain branched polymers and its absence in the case of the linear polymer, the stronger decrease of the tensile compliance in comparison to the shear compliance with increasing stress, as well as the extended linear-viscoelastic regime of the shear viscosity in contrast to the shear compliance are correctly modeled. While the modeling of the nonlinear response in shear can be achieved with only one material parameter for most of the polymers considered here, the nonlinear modeling in elongation is achieved with two parameters. The same parameter values are shown to describe viscous as well as elastic properties of the melts, and thus the relations of Laun can be used to test the consistency of viscosity and compliance measurements.
Keywords: Rheology; Creep experiments; Shear flow; Elongational flow; Damping function; Strain hardening; Low-density polyethylene; Polymer melts

Preparation of magnetorheological elastomers and their slip-free characterization by means of parallel-plate rotational rheometry - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (Smart Materials and Structures, 2017)
A systematic study is presented to highlight a methodology of sample preparation and subsequent slip-free characterization of magnetorheological (MR) elastomers in parallel-plate rotational rheometry. Focusing on the magnetic field-dependent nonlinear viscoelastic behavior an array of oscillatory strain sweep measurements is conducted with samples cured within the rheometer. The examined nonlinear material response (i.e. the amplitude dependence of the storage and loss moduli) as a function of the applied magnetic field is found to be qualitatively similar to the amplitude dependence of particle reinforced elastomers (i.e. the Payne effect). Therefore, the experimental data (both moduli) is decomposed similar to that for reinforced elastomers and a phenomenological model is formulated for both the storage and loss modulus to account for the physical mechanisms governing the nonlinear material characteristics. Parameter identification suggests that the material response at low magnetic fields is dominated by the polymeric network whereas the strong magneto-reinforced microstructure governs the linear and nonlinear viscoelastic behavior at high magnetic fields. The overall experimental outcome further suggests that the underlying concept of the phenomenological model for particle reinforced elastomers (i.e. destruction and reformation of the filler network) can be transfered to magnetorheological materials. Consequently, the proposed phenomenological model can be applied to quantify and further analyze the nonlinear response characteristics of MR elastomers (i.e. the amplitude dependence of the storage and loss modulus as a function of the applied magnetic field) that is closely linked to microstructural changes of the magnetizable particle network.
Keywords: Magnetorheological Elastomers (MREs); Field-Responsive Materials; Large Amplitude Oscillatory Shear (LAOS); Magnetorheometry; Magneto-Induced Payne Effect

Probing structure changes in magneto-rheological fluids and elastomers based on an injection moldable liquid silicone - Kaschta, Joachim; Musialek, Matthias; Böse, Holger; Schubert, Dirk W. (8th Annual European Rheology Conference, 2013)

Processing and characterisation of alginate-based hydrogels for the application in 3-D Bio Platting - Detsch, Rainer; Zehnder, Tobias; Sarker, Bapi; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (14th BIONANO-MATERIALS, 2013)

Production of polyamide 11 microparticles for Additive Manufacturing by liquid-liquid phase separation and precipitation - Dechet, Maximilian; Goblirsch, Anja; Romeis, Stefan; Zhao, Meng; Lanyi, Franz; Kaschta, Joachim; Schubert, Dirk W.; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Chemical Engineering Science, 2019)
Within this contribution liquid-liquid phase separation (LLPS) and precipitation from ethanol was studied as an approach to produce polyamide 11 (PA11) powders for selective laser sintering (SLS). To this end, the cloud point and solution temperature curve of the PAll-ethanol system was determined experimentally via turbidity measurements. The proper range of system composition and temperature for particle formation was deduced. The dependence of particle characteristics on process parameters (polymer concentration, stirring conditions and temperature regime) during LLPS and precipitation was assessed and the products were characterized with respect to their size and morphology. Furthermore, structural, rheological and thermal characteristics were analyzed and correlated with process parameters. Molecular weight distributions were determined. After removal of fines and dry coating with hydrophobic fumed silica, an optimized PA11 powder with mean particle size of 91 mu m showing good flowability for SLS was obtained. SLS processability of this optimized PA11 powder was demonstrated by building multilayered test specimens in a laser sintering machine. With this contribution, we present a comprehensive workflow for the process development, product characterization and product application of a SLS powder manufactured via precipitation. (C) 2018 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-02-21

Quality monitoring of PE-X semi-finished products - Heiduk, I.; Falk, M.; Schubert, Dirk W.; Kaschta, Joachim (Kunststoffe International, 2015)

Quality Monitoring of PE-X Semi-Finished Products - Heiduk, Ines; Falk, Martin; Schubert, Dirk W.; Kaschta, Joachim (Kunststoffe International, 2015)
In industrial production monitoring, fast, reliable results are required to evaluate product quality. Suitable test methods must be available for this purpose. The time-consuming method previously used to determine the degree of crosslinking of PE-X pipes can now be replaced by rapid rheological measurements

Recycling and Reprocessing of Thermoplastic Polyurethane Materials towards Nonwoven Processing - Wölfel, Bastian; Seefried, Andreas; Allen, Vincent; Kaschta, Joachim; Holmes, Christopher; Schubert, Dirk W. (Polymers, 2020)
Thermoplastic Polyurethane (TPU) is a unique tailorable material due to the interactions of hard and soft segments within the block-copolymer chain. Therefore, various products can be created out of this material. A general trend towards a circular economy with regards to sustainability in combination with TPU being comparably expensive is of high interest to recycle production as well as post-consumer wastes. A systematic study investigating the property changes of TPU is provided, focusing on two major aspects. The first aspect focuses on characterizing the change of basic raw material properties through recycling. Gel permeation chromatography (GPC) and processing load during extrusion indicate a decrease in molar mass and consequently viscosity with an increasing number of recycling cycles. This leads to a change in morphology at lower molar mass, characterized by differential scanning calorimetry (DSC) and visualized by atomic force microscope (AFM). The change in molar mass and morphology with increasing number of recycling cycles has an impact on the material performance under tensile stress. The second aspect describes processing of the recycled TPU to nonwoven fabrics utilizing melt blowing, which are evaluated with respect to relevant mechanical properties and related to molecular characteristics. The molar mass turns out to be the governing factor regarding mechanical performance and processing conditions for melt blown product
Keywords: recycling; reprocessing; TPU; thermoplastic elastomers; TPE; thermoplastic; polyurethane; elastomers; nonwoven; processing; melt blown; molar mass; mechanical properties; methylendiphenylisocyanate; MDI; polytetramethylene glycol; PTMG; morphology; structure; phase separation; sustainability; circular economy

Reliable determination of the cross-link density in crosslinked polyethylenes by a new rheologicial measurement - Kaschta, Joachim; Falk, M.; Heiduk, I.; Walter, Lisa; Schubert, Dirk W. (Abstracts, 2016)

Resonance phenomena in oscillatory shear rheometry: Influence of material parameters - Redel, Michael; Walter, Bastian; Kaschta, Joachim; Steinmann, Paul; Schubert, Dirk W. (Nordic Polymer Days 2018, 2018)
Rheological measurements are an established method for the characterisation of dynamic mechanical polymer properties. In current literature, possible restrictions to thesemeasurements by the phenomenon of resonance were evaluated by Stettin [1]. However, this paper is quiet about the influence of material parameters like stiffness or damping on the resonance phenomenon Therefore, an unfilled silicone elastomer, free of material particle interactions, is used. The cylindrical specimen are cured in a rheometer binding them firmly to the rotor. This has proven to prevent occurrence of for example wall slip [2]. The experiments conducted are frequency sweeps by means of a parallel-plate rheometer with a smooth geometry surface. Consequently, the influence of the setup, which was detected by Stettin [1], can be neglected. Resulting resonance frequencies are analysed concerning the material's damping and stiffness. Change in these parameters is realised by variation of mixture as well as addition of an additive. The resulting resonance frequencies show an explicit dependency of complex shear modulus |G*| as a measure of the stiffness. The resulting dependence in double logarithmic plot is compared with resonance frequency calculations based on oscillatory theories. Contribution of varying damping, realised by changing loss factor tan(δ), is detectable as an additional shift in resonance frequency and also discussed. Intriguingly, the wavedata of the stress response after resonance, obtained via fast Fourier transformation, differs from the expected sinusoidal signal. The change in wavedata and aberration from the sinusoidal excitation is explained by the phenomenon of vibration isolation. Furthermore, it is correlated with the material’s parameters reasoning the different experimental outcomes caused by the change in composition. A guideline to avoid the influence of resonance on oscillatory measurements is lastly presented

Ressourcenschonende Verpackungen aus PET durch reaktive Extrusion mit niedermolekularen Substanzen - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Würzburger Tage 2014, 2014)

Revealing the effects of aerosol deposition on the substrate-film interface using NaCl coating - Khansur, Neamul H.; Eckstein, Udo; Li, Yizhe; Hall, David A.; Kaschta, Joachim; Webber, Kyle Grant (Journal of the American Ceramic Society, 2019)
Aerosol deposition is a feasible method of fabricating dense ceramic films at room temperature by the impact consolidation of submicron‐sized particles on ceramic, metal, glass, and polymer substrates at a rapid rate. Despite the potential usefulness of the aerosol deposition process, there are issues, such as deposition mechanisms and structure of the film‐substrate interface, that are not well understood. We have used complementary structural and microstructural analysis to capture the state of the substrate surface after the aerosol deposition process. The results reveal that modification of the substrate surface by the ejected submicron‐sized particles is essential for the formation of anchoring layer, thereby, a change in internal residual stress state and surface free energy of the substrate is required to deposit film using AD process. Our analysis also suggests that the adhesion between the metal substrate and ceramic particles is possibly contributed by both physical bonding and mechanical interlocki
Keywords: stress; thick films; X-ray methods

Revealing the effects of aerosol deposition on the substrate‐film interface using NaCl coating - Khansur, Neamul Hayet; Eckstein, Udo; Li, Yizhe; Hall, David A.; Kaschta, Joachim; Webber, Kyle Grant (Journal of the American Ceramic Society, 2019)
Aerosol deposition is a feasible method of fabricating dense ceramic films at room temperature by the impact consolidation of submicron‐sized particles on ceramic, metal, glass, and polymer substrates at a rapid rate. Despite the potential usefulness of the aerosol deposition process, there are issues, such as deposition mechanisms and structure of the film‐substrate interface, that are not well understood. We have used complementary structural and microstructural analysis to capture the state of the substrate surface after the aerosol deposition process. The results reveal that modification of the substrate surface by the ejected submicron‐sized particles is essential for the formation of anchoring layer, thereby, a change in internal residual stress state and surface free energy of the substrate is required to deposit film using AD process. Our analysis also suggests that the adhesion between the metal substrate and ceramic particles is possibly contributed by both physical bonding and mechanical interlocking.<br
Keywords: stress; thick films; X‐ray methods

Reversal phenomena of molten immiscible polymer blends during creep-recovery in shear - Pan, Yamin; Liu, Xian Hu; Kaschta, Joachim; Liu, Chuntai; Schubert, Dirk W. (Journal of Rheology, 2017)
In this work, the creep- recovery behavior of immiscible poly (styrene)/poly (methyl methacrylate) blends and their pure components in the molten state were systematically investigated. A stationary plateau in the recoverable compliance of pure components is observed. Unexpectedly, for immiscible polymer blends, the recoverable compliances show different phenomena. For blends with a fine co-continuous morphology, the recoverable compliances exhibit a one-reversal phenomenon, whereas a two-reversal phenomenon is found in the blends with a sea-island morphology. Moreover, these reversal behaviors become less pronounced with decreasing temperature, increasing creep stress, increasing annealing time, or incorporation of nanoparticles. Three competitive effects, i.e., the recovery of oriented polymer matrix, the interfacial tension which drives the deformed droplets to their equilibrium shape, and the phase coarsening process, are used here to explain the different behaviors. (C) 2017 The Society of Rheology.

Rheological and thermo-mechanical properties of Polylactide/Poly(methylmethacrylacte) blends - Hao, Xiaoqiong; Kaschta, Joachim; Schubert, Dirk W. (10th Annual European Rheology Conference, 2015)

Rheological examination and 3D bioprinting of pre-gelled alginate hydrogels - Hazur, Jonas; Kaschta, Joachim; Bednarzig, Vera; Boccaccini, Aldo R.; Schubert, Dirk W.; Detsch, Rainer (Nordic Polymer Days 2018, 2018)
lginate hydrogels are from special interest in wound healing, drug delivery and tissue engineering applications, due to their biocompatibility and similarity to the extracellular matrices in tissues [1]. In this project, bioprinting of pre-crosslinked medical grade alginate gels via an internal gelation method using D-(+)-Gluconic acid-lactone in combination with CaCO3 was implemented and the rheological characteristics of the gels were examined. By parameter optimization, it was possible to print 3D porous structures with a height of 5 mm and a pore size of 1.1 mm with those gels. Surprisingly, the stirring process during cross-linking turned out to play a major role for the absolute value of complex viscosity (|η*|), as well as for the homogeneity of the gels. A significant increase of |η*| as well as of the storage modulus was obtained, when the gels were not stirred, leading to gels without viscous flow and therefore to less defined printed structures. Apart from that, the temperature during pre-crosslinking plays an important role on the homogeneity. At lower temperatures than room temperature, the gels showed a more uniform gelation process, compared to those at 20 °C. Furthermore, the concentration and temperature dependence of the alginate solutions were rheologically characterized. The shear dependent viscosities were superposable for both temperature and concentration and appropriate fitting functions in the investigated regions were derive

Rheological monitoring of the cross-link density for polyethylene materials cross-linked using different cross-linking technologies - Kaschta, Joachim; Heiduk, I.; Falk, M.; Schubert, Dirk W. (Book of Abstracts, 2016)

Rheological properties of LDPE/LLDPE-blends in the molten state in shear and elongation - Kaschta, Joachim; Dörgens, Anna; Schubert, Dirk W. (10th Annual European Rheology Conference, 2015)

Rheological study of the reaction kinetics in a poly(ethylene terephthalate) melt - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Polymer Degradation and Stability, 2015)
Time dependent measurements of the zero shear viscosity are applied to study the thermal stability of a commercial poly(ethylene terephthalate). Firstly, the factors influencing the experimental results, like moisture content and type of atmosphere (air or nitrogen) are briefly reviewed. Secondly, the time dependent viscosity is studied on dry samples in nitrogen atmosphere at various temperatures, as these conditions are commonly used for the rheological material characterization. All viscosity curves show a characteristic maximum which strongly depends on time and temperature. This maximum reflects the changes in molar mass resulting from the various chemical reactions. A simplified kinetic model, based on one build-up and one degradation reaction, is derived and used to analyze the experimental data. This model enables to determine the activation energy of flow (65 kJ mol(-1)) and the activation energy resulting from the temperature dependence of the molar mass maximum (120 kJ mol(-1)). Kinetic constants and corresponding activation energies of the chemical reactions are determined as well. The comparison with literature shows that the activation energies are similar to those found for the polymerization process. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Poly(ethylene terephthalate); Rheology; Reaction kinetics; Thermal degradation; Activation energy

Rheologisches Verhalten magnetorheologischer Fluide und Elastomere auf Basis von Flüssigsilikon - Kaschta, Joachim; Walter, Bastian; Musialek, Matthias; Schubert, Dirk W. (Geesthachter Polymertage: Praktische Rheologie von Polymeren – Grundlagen und Anwendungen, 2014)

Selective Laser Sintering of Polyetheretherketone for bone substitutes - Pohle, D.; Rechtenwald, T.; Kaschta, Joachim; Münstedt, H. (Proceedings of the 10th International Conference on Polymers in Medicine and Surgery, 6.-8. September, Cambridge, 2004)
LFT Import::2019-08-05 (1114)

Shear and Elongational Flow Properties of Long-Chain Branched Poly(ethylene terephthalates) and Correlations to Their Molecular Structure - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Macromolecules, 2014)
Reactive processing with low-molar-mass modifiers is a well-known method to create long-chain branched (LCB) structures in a poly(ethylene terephthalate) (PET) melt. However, less is known about the elongational flow properties of LCB-PET. Therefore, the aim of this contribution is (a) to generate LCB molecules and (b) to evaluate the influence of the branching level on the transient elongational behavior. For this purpose, a commercial, linear PET and different contents (0.1-0.3 wt %) of the tetrafunctional modifier pyromellitic dianhydride (PMDA) were reactively processed. All samples were analyzed by size exclusion chromatography coupled with a light scattering device and characterized by shear and elongational rheometry. It was found that the molar mass distribution of the modified materials exhibit a high molar mass shoulder, leading to an increase of the weight-average molar mass and a broadening of the molar mass distribution. Moreover, the Mark-Houwink plot of the modified materials displays deviations from the power law toward lower intrinsic viscosities, which indicate the existence of LCB molecules. The shear viscosity shows a pronounced shear thinning behavior and a remarkable increase at low frequencies compared to the linear PET. Considering the transient elongational viscosity, a distinguished strain hardening is observed, which increases with increasing PMDA content and with increasing strain rate. From the results of the rheological and molecular characterization and by considering the chemical reaction mechanisms, it can be concluded that the PET modified with high PMDA contents has a treelike branch-on-branch architecture, which is well-known from low-density polyethylene melts.

Shear and elongational flow properties of peroxide-modified wood/low-density polyethylene composite melts - Harnnarongchai, Wanlop; Kaschta, Joachim; Schubert, Dirk W.; Sombatsompop, Narongrit (Polymer Composites, 2012)
Adding fillers to a polymer melt may result in a strain softening behavior in elongational flow in long-chain branched materials, showing strain-hardening behavior when compared with unfilled one. To improve the strain-hardening properties in wood/LDPE composites, the effect of peroxide concentration on both the molecular architecture and molar mass distribution, and the rheological quantities in shear and elongation is studied. Addition of wood flour increases the viscosity according to a logarithmic mixing rule, as expected from the large particle size and the filler fractions used. The peroxide has multiple effects on the molar architecture of the polymer. First, a gel fraction of cross-linked material is formed, the concentration of gel being dependent of the amount of peroxide used. Second, a higher molar mass component is detected, leading to higher value of Mw and to a broader molar mass distribution. Finally, the degree of long-chain branching unexpectedly decreases with increasing peroxide content. The changes in molecular architecture are hardly influenced by addition of the wood flour. The peroxide treatment leads to an improved strain-hardening behavior, detected by elongational viscosity and melt strength measurements. However, the addition of wood flour decreases the amount of strain hardening.

Size Effect of Silica Particles on the Rheological Properties of Polyactide - Hao, Xiaoqiong; Kaschta, Joachim; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Soft–matrices based on Fibrous Proteins for Biofabrication - Silva Lourenco, Rauqel; Sarker, Bapi; Singh, Raminder; Cicha, Iwona; Roether, Judith; Kaschta, Joachim; Detsch, Rainer; Garlichs, Christoph; Schubert, Dirk W.; Boccaccini, Aldo R. (14th BIONANO-MATERIALS, 2013)

Soft-matrices based on silk fibroin and alginate for tissue engineering - Silva, Raquel; Singh, Raminder; Sarker, Bapi; Papageorgiou, Dimitrios G.; Juhasz, Judith A.; Roether, Judith; Cicha, Iwona; Kaschta, Joachim; Schubert, Dirk W.; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2016)
Keywords: Alginate; Endothelial cells; Silk fibroin; Soft-matrix; Tissue engineering

Sonochemical processing and characterization of composite materials based on soy protein and alginate containing micron-sized bioactive glass particles - Silva Lourenco, Rauqel; Bulut, Buse; Roether, Judith; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Journal of Molecular Structure, 2014)
Novel composite hydrogels based on the combination of natural polymers; namely alginate and soy protein isolate, and bioactive glass (BC) particles (mean size: 2 pm) were developed. For this purpose a sono-chemical approach was used and homogeneous composite hydrogels, incorporating two concentrations of BC particles, were successfully obtained. Further physico-chemical characterization was performed in order to evaluate the influence of each component on hydrogel properties. The water uptake ability, weight loss, protein release, as well as FTIR, SEM and DMTA characterization were carried out. The bio-mineralization process in simulated body fluid (SBF) was followed over time and the results demonstrated that the composite materials have the ability to form a surface apatite layer after 7 days in SBF. The design of novel composite hydrogels based on soy protein, alginate and BC can be a suitable approach for bone regeneration applications. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Alginate; Soy isolate protein; Bioactive glass; Hydrogel; Tissue engineering

Spray-coatable ionogels based on silane-ionic liquids for low voltage, flexible, electrolyte-gated organic transistors - Thiemann, Stefan; Sachnov, Swetlana; Gruber, Mathias; Gannott, Florentina; Spallek, Stefanie; Schweiger, Manuel; Krückel, Johannes; Kaschta, Joachim; Spiecker, Erdmann; Wasserscheid, Peter; Zaumseil, Jana (Journal of Materials Chemistry C, 2014)
We introduce a new type of silane-based ionogels that are produced by gelation of the ionic liquid 3-methyl-1-(3-(triethoxysilyl)propyl)-imidazolium bis(trifluoromethylsulfonyl)imide ([(EtO)3SiPMIM][TFSI]) with tetramethylorthosilane and formic acid. In the obtained ionogels the cations are involved in the network formation while the anions can move freely. The ionogels show advantageous properties for application in flexible electronics, such as low modulus, solution processability and high specific capacitance. Spray-coated ionogels were used as high capacitance gate dielectrics for organic (poly[3-hexylthiophene], P3HT) electrolyte-gated transistors (EGTs) that operated at very low voltages (<2 V) with high on/off ratios in air over weeks. Devices fabricated on polymer foil remained functional during repeated bending cycles with strains up to 2.3%.

Sterilization effects on the physical properties and cytotoxicity of poly (glycerol sebacate) - Rai, Ranjana; Tallawi, Marwa; Roether, Judith; Detsch, Rainer; Barbani, Niccoletta; Rosellini, Elisabeth; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Letters, 2013)
The influence of conventional sterilization methods such as gamma irradiation, ethylene oxide treatment and steam exposure on the physical properties of poly(glycerol sebacate) (PGS) was investigated. Scanning electron microscope (SEM) observations, attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and Raman spectra demonstrated that the applied sterilization methods do not induce adverse surface modifications. The sterilized samples also maintained their thermal and mechanical properties post-sterilization. In addition, gamma sterilized PGS films did not induce any toxicity when films were in contact with murine fibroblast 313 cells. PGS is compatible for all the sterilization methods used in this study, which is of relevance for the wider application of PGS in medical devices. (C) 2013 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.steril
Keywords: Biocompatibility; Biopolymers; Gamma irradiation; Poly(glycerol sebacate); Sterilization

Studies on Recycled Polyester - Qin, Yijing; Qu, Muchao; Kaschta, Joachim; Allen, Vincent; Schubert, Dirk W. (Textile Science and Clothing Technology, 2019)
In this chapter, poly(ethylene terephthalate) (PET) melt-spun fibres from five different PET materials were fabricated by a capillary rheometer, which was equipped with an air aspirator for aerodynamic stretching. Two recycled PET of coloured rPET-A and clear rPET-B from waste PET bottle flakes were used, and three virgin PET with different grades of the bottle-grade vPET-2, fibre-grade vPET-1 and fibre-grade vPET-3 were chosen as reference benchmark. During the extrusion process, two processing temperatures of 270 and 280 °C in the capillary rheometer were applied, combined with six different take-up pressures from 0.5 to 3.0 bar for fibre stretching during the spinning process. An empirical equation was given, to predict the water content of PET materials under the specific drying temperature and drying time. Afterwards, the characteristics of the raw materials and drawn PET fibres were discussed comprehensively from the perspective of thermal behaviour, molar mass characteristic, rheological properties, surface morphology, diameter, tenacity and elongation at break. rPET-B and vPET-1 materials yielded optimal spinnability and demonstrated to be the most suitable materials to fabricate fibres with a desirable tenacity, an outstanding elongation at break and an excellent fibre fineness. Crystallinity and orientation of fibres from these two materials were explored to give a potential explanation for the higher tenacity. Furthermore, performance-reliability plots were applied, and a semi-empirical equation was suggested for the first time relating the tenacity and elongation at break of fibres. This study proves the possibility to produce PET fibres from bottle-grade recycled co-polymer PET material, which have similar properties as fibres produced from fibre-grade virgin homo-polymer PET. All the specific information of the five investigated PET materials, especially rPET-B and vPET-1, can provide guidance for melt spinning process in the futur
Keywords: Recycled PET Virgin PET Melt spinning Thermal behaviour Viscosity Surface morphology Mechanical property Semi-empirical equation

Superalloy IN625 with cellular microstructure - Fabrication route and mechanical properties - Quadbeck, Peter; Kaschta, Joachim; Singer, Robert (Advanced Engineering Materials, 2004)
Cellular microstructures are of special interest for applications in filtering, heat transfer or acoustic absorption. In the present paper a new route for the preparation of such structures from superalloys will be presented. Polyoxymethylene (POM) is used as space holder which can be injection molded into any desired shape. Densification of the cell walls and struts is achieved by supersolidus liquid phase sintering (SLPS).

Synthesis and Characterization of Novel Ethylene-graft-Ethylene/Propylene Copolymers - Stadler, Florian; Arikan, Burçak; Kaschta, Joachim; Kaminsky, Walter; Münstedt, Helmut (Macromolecules, 2011)
A sequential metallocene-catalyzed synthesis of ethylene/propylene macromers, which are subsequently incorporated into growing polyethylene chains, leads to comb-like polymers. After the synthesis, a Soxhlet extraction ensures the purity of the sample. The GPC-MALLS analysis reveals narrowly distributed samples with a non-negligible degree of branching. The comb polymers show a very high viscosity, which significantly differs from conventional long-chain branched metallocene polyethylenes (LCB-mPE) but is in agreement with findings on comb model polymers. The zeroshear rate viscosity eta(o) lies significantly above the relation between M(w) and eta(o) for linear and for conventional LCB-mPE. The thermorheological behavior is complex and differs from that observed for LCB-mPE but also does not resemble an LDPE-like thermorheological behavior.

Temperature Dependence of DC Dielectric Strength and Voltage Endurance of BOPP - Werner, Siegfried; Kellner, Michael; Kaschta, Joachim; Schubert, Dirk W. (Annual Report - Conference on Electrical Insulation and Dielectric Phenomena, CEIDP, 2023)
Biaxially oriented polypropylene (BOPP) is the current gold standard for DC thin film capacitors. However, one of its major disadvantages is the poor high-Temperature stability. It is the aim of this study to contribute to the understanding of the failure of BOPP at elevated temperatures. Therefore, capacitor-grade PP was extruded into a cast film using a twin-screw extruder and a water-cooled chill roll. BOPP films were produced using a laboratory stretching machine. The films were tested for their short-Term dielectric strength and voltage endurance between 23 and 140°C. DSC, shrinkage and TSDC measurements were conducted to analyze the morphological and electrical changes in the material at elevated temperatures. An increase in temperature caused a reduction in dielectric strength and voltage endurance. The onset of space charge release by thermal trap activation coincided with a slow deterioration in both properties. The decrease was further enhanced as crystalline regions of low stability started to melt and orientation in amorphous regions started to be relaxed. This shows that trap states and morphological changes in the operating temperature range of thin film capacitors between 60 and 100°C should be the focus of future research.
CRIS-Team Scopus Importer:2024-12-16
Keywords: BOPP; dielectric strength; failure; temperature; voltage endurance

The influence of nanoparticles and their functionalization on the dielectric properties of biaxially oriented polypropylene for power capacitors - Streibl, Maximilian; Werner, Siegfried; Kaschta, Joachim; Schubert, Dirk W.; Moos, Ralf (IEEE Transactions on Dielectrics and Electrical Insulation, 2020)
In this work, eleven commercially available nanoparticles are benchmarked against each other according to their potential for an application in a polypropylene (PP) based nanocomposite for thin film power capacitors. Biaxially oriented films containing a fixed concentration of 5 wt%. Al2O3, TiO2, SiO2, or POSS nanoparticles with different surface functionalization were analyzed by dielectric spectroscopy and dielectric breakdown measurements. Two particle systems emerged to increase both the dielectric breakdown strength and the reliability of the films combined with low dielectric losses. The effects of the particles were in agreement with the multicore model of Tanaka et al. The particle dispersion was analyzed on SEM images. A correlation between agglomerates and zeta potential in isopropanol was found yielding a quick analysis tool for the tendency of nanoparticles to form clusters during processing with PP. To assure comparability between the films, the real particle content was determined by incineration. The surface roughness of the film has a large influence on the breakdown behavior and was, therefore, also monitored.
CRIS-Team Scopus Importer:2020-04-14
Keywords: dielectric breakdown; dielectric films; dielectric losses; dielectric materials; nanocomposites

Thermal stabilization of polypropylene by renewable antioxidants - Kröner, Richard; Kaschta, Joachim; Heiduk, Ines; Dorfmüller, Daniel; Falk, Martin; Schubert, Dirk W. (2023)
The thermal stability of recycled polypropyl- ene should be increased by using renewa- ble stabilizers known as antioxidants. These chemical compounds delay the degradation and aging of polymers by offering a hydrogen atom to the radical generated during thermal decomposition, so that the radical does not react with the polymer chain [1]. In this work the use of Irganox 1010 (industry standard), lignin and α-tocopherol (vitamin E) in polypropylene is investigated [2-4]. To assess the effectiveness of the stabilizers, the oxidation induction time (OIT) is determined according to standard (EN ISO 11357-6) [5]. The oxidation induction time is the time a polymer can resist at 200 °C until degradation occurs after the change from nitrogen to oxygen atmosphere. The objective is to increase that time to more than 10 minutes. By adding different amounts of antioxidant, a critical concentration c* is cal- culated at which the objective is achieved. A linear relationship between concentration and thermal stability is found for all systems, except for the addition of α-tocopherol. The highest thermal stability is achieved by α-to- copherol and α-tocopherol succinate, whose structures are formed on the basis of BHA (2, 6-di-tert-butyl-4-methoxyphenol) instead of BHT (2, 6-di-tert-butyl-4-methylphenol), as it is the case for the other stabilizers [4]. Compared to the industry standard (Irganox 1010) the efficiency of α-tocopherol is ten times higher in the relevant concentration level, making Vi- tamin E the most suitable antioxidant found in this research. The wood component lignin also shows good stabilization effects, but requires the tenfold concentration c* than Irganox 1010. Furthermore, the stabilized samples are ana- lysed with regard to their rheological proper- ties. At a temperature of 250 °C, that is equal to the processing temperature in the industry, degradation occurs during the measurement, so the unstabilized sample (pure PP) shows a lower viscosity compared to the stabilized sampl

Thermodynamically Consistent Model to Predict the Magneto-Rheological Behavior of Magneto-Sensitive Elastomers - Saxena, Prashant; Walter, Bastian; Kaschta, Joachim; Fey, Tobias; Steinmann, Paul; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Thermorheological behavior of various long-chain branched polyethylenes - Stadler, Florian; Kaschta, Joachim; Münstedt, Helmut (Macromolecules, 2008)
To analyze the thermorheological behavior of various polyethylenes, the relaxation spectra were shifted. Not only linear and short-chain branched PE but also the classical high-pressure LDPE were found to be thermorheologically simple, i.e., the activation energy E(a) is independent of the relaxation strength or the relaxation time, respectively. However, for the long-chain branched metallocene catalyzed polyethylenes investigated a significant dependence of the activation energy E(a) on the relaxation time is detected. At shorter relaxation times E(a) is very close to that of linear PE, but it increases with longer times. The lower E(a) values are assumed to be due to linear molecules and the higher ones to different species of long-chain branched molecules. These findings offer the possibility to use the analysis of the thermorheological complexity to get an insight into the branching structure of polyethylenes. For the LCB-mPE investigated, it can be concluded that they are a mixture of linear and long-chain branched chains.

Thermorheological Behavior of Various Short- and Long-Chain Branched Polyethylenes and Their Correlations with the Molecular Structure - Keßner, Ute; Kaschta, Joachim; Stadler, Florian; Le Duff, Cécile; Drooghaag, Xavier; Münstedt, Helmut (Macromolecules, 2010)
This paper deals with the characterization of a broad range of linear polyethylenes (PE) by means of thermorheology. It is demonstrated, in which way the thermorheological behavior can be related to the comonomer type and content of copolymers. In the first part of this paper, well-established analytical and theological methods are applied to distinguish linear and branched samples. The resolution limit of these methods is demonstrated by the investigation of a blend from a linear-low density PE (LLDPE) and a branched low density PE (LDPE). Special attention is paid to nuclear-magnetic resonance (NMR) spectroscopy in order to reliably determine the comonomer type and content of the samples chosen. The main focus of this paper lies on thermorheological investigations and correlations with the molecular structure. The comparatively high sensitivity of such investigations is highlighted: even small amounts of long-chain branches (LCB) are revealed. The activation energy (E(u)) of linear samples increases with growing comonomer length and content, respectively. As such, thermorheology is demonstrated to be an interesting theological "tool" to get an insight into branching structures. Moreover, the experimental effort is relatively small as solely usual dynamic-mechanical experiments at different temperatures are required.

TiO2-PLLA nanocomposite coatings and free-standing films by a combined electrophoretic deposition-dip coating process - Chavez-Valdez, Alejandra; Arizmendi-Morquecho, Ana; Moreno Bello, Karla; Roether, Judith; Kaschta, Joachim; Boccaccini, Aldo R. (Composites Part B-Engineering, 2014)
TiO2/PLLA nanocomposites were prepared using a two-step process involving electrophoretic deposition (EPD) and dip coating (DC). EPD was carried out first to obtain porous TiO2 nanostructured coatings while subsequent dip coating was performed using different concentrations of PLLA in dichloromethane (DCM) to obtain nanocomposite materials. According to SEM images, cracks in the TiO2 nanostructured coatings, developed upon drying, were filled with the polymer which led to improvement of the flexibility of the nanocomposite coatings. Similarly, a surface modification from hydrophilic to hydrophobic was obtained with the addition of the polymer. FTIR analysis showed characteristic bands of both materials, TiO2 and PLLA, both on the coating surface and at the interphase between the nanocomposite coating and the substrate. Hardness measurements showed a maximum value of 1.4 GPa for TiO2-10 wt% PLLA composite. For DMTA tests, detached layers were used and the storage and loss moduli were determined. TiO2-PLLA nanocomposite coatings showed higher values of storage modulus at higher temperature in comparison to pure PLLA samples. Also, there was a shift in the glass transition temperature (T-g) with increasing TiO2 content. In conclusion, the EPD-DC combined technique proposed here enables the fabrication of nanostructured coatings and free-standing layers in which the quantity of PLLA can be changed according to the intended application, i.e. it is possible to fabricate coatings with tailored degradability and suitable mechanical properties with low additions of PLLA or free standing films with increased flexibility, biodegradability and biocompatibility with high amounts of PLLA. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures; Particle-reinforcement; Mechanical properties; Surface properties; Electrophoretic deposition

TiO2-PLLA nanocomposite coatings and free-standing films by a combined electrophoretic deposition-dip coating process - Chavez-Valdez, Alejandra; Arizmendi-Morquecho, Ana; Moreno, K. J.; Roether, Judith; Kaschta, Joachim; Boccaccini, Aldo R. (Composites Part B-Engineering, 2014)
TiO2/PLLA nanocomposites were prepared using a two-step process involving electrophoretic deposition (EPD) and dip coating (DC). EPD was carried out first to obtain porous TiO2 nanostructured coatings while subsequent dip coating was performed using different concentrations of PLLA in dichloromethane (DCM) to obtain nanocomposite materials. According to SEM images, cracks in the TiO2 nanostructured coatings, developed upon drying, were filled with the polymer which led to improvement of the flexibility of the nanocomposite coatings. Similarly, a surface modification from hydrophilic to hydrophobic was obtained with the addition of the polymer. FTIR analysis showed characteristic bands of both materials, TiO2 and PLLA, both on the coating surface and at the interphase between the nanocomposite coating and the substrate. Hardness measurements showed a maximum value of 1.4 GPa for TiO2–10 wt% PLLA composite. For DMTA tests, detached layers were used and the storage and loss moduli were determined. TiO2–PLLA nanocomposite coatings showed higher values of storage modulus at higher temperature in comparison to pure PLLA samples. Also, there was a shift in the glass transition temperature (Tg) with increasing TiO2 content. In conclusion, the EPD–DC combined technique proposed here enables the fabrication of nanostructured coatings and free-standing layers in which the quantity of PLLA can be changed according to the intended application, i.e. it is possible to fabricate coatings with tailored degradability and suitable mechanical properties with low additions of PLLA or free standing films with increased flexibility, biodegradability and biocompatibility with high amounts of PLLA.
Keywords: B. Mechanical properties; B. Surface properties; A. Nanostructures; A. Particle-reinforcement; Electrophoretic deposition

Versagen von Silikonbrustimplantaten - Neuartige Kartierung und Aufdeckung von Produkt-Clustern - Daenicke, Jonas; Walter, Bastian; Horch, Raymund E.; Kaschta, Joachim; Schubert, Dirk W. (Plastische Chirurgie, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-TM.versag

Viscoelastic and electrical behavior of poly(methyl methacrylate)/carbon black composites prior to and after annealing - Pan, Yamin; Liu, Xian Hu; Kaschta, Joachim; Hao, Xiaoqiong; Liu, Chuntai; Schubert, Dirk W. (Polymer, 2017)
Keywords: Carbon black; Creep-recovery; Polymer nanocomposites; Viscoelastic properties

Viscosity and Softening Behavior of Alkali Zinc Sulfophosphate Glasses - Da, Ning; Krolikowski, Sebastian; Nielsen, Karsten H.; Kaschta, Joachim; Wondraczek, Lothar (Journal of the American Ceramic Society, 2010)
We report on the softening properties and viscosity of glasses from the system ZnO–Na_2O–SO_3–P_2O5 for low-temperature sealing applications. Up to a ratio of network-forming ions PO_43-:SO_42- of about 2:1, a gradual substitution of P_2O5 by SO_3 results in decreasing glass transition and softening temperatures. At the same time, decreasing kinetic fragility is observed, noteworthy even for decreasing the total amount of network former from 44 at.% to 39 at.%. Thermomechanical and calorimetric analyses reveal a distinct SO_42–promoted relaxation phenomenon at temperatures significantly below the macroscopic glass transition temperature, which is interpreted as a result of the formation of an increasingly interconnected assembly of SO_42- and PO_43- units with increasing SO_3 content.
EAM Import::2019-03-12

Viscous and elastic properties of polylactide melts filled with silica particles: Effect of particle size and concentration - Hao, Xiaoqiong; Kaschta, Joachim; Schubert, Dirk W. (Composites Part B-Engineering, 2016)
Mixing of inorganic particle into polymer material is widely used to tailor polymer with desired physical properties and processibility, in which the size and concentration of the former play a critical role in polymer processing. In this study, rigid spherical silica particle with varying size (average diameter of 7 nm, 40 nm, and 9 mu m) were used to reinforce polylactide (PLA) by melt compounding. The dependence of rheological properties of PLA/silica composites on the silica size and concentration were examined by dynamical mechanical and creep-recovery experiments. Our results demonstrate that mixing of silica particles into PLA matrix could increase the thermal stability of PLA. Oscillatory shear tests in the linear viscoelastic regime revealed a strong concentration-dependent behavior for the storage, loss moduli, and complex viscosity of the PLA/silica composites by the addition of nanosilica, while these properties were slightly affected by the addition of microsilica at low frequency range. A linear relationship between the silica concentration and the logarithmic form of zero shear viscosity (log eta(0)) of the composites is found when the concentration is below the rheological percolation threshold, whereas the growth rate is inversely influenced by the silica particle size. Creep-recovery experiments indicated that the elastic properties of PLA were more sensitive by the addition of silica than the viscous properties. Even for microsilica, a remarkable enhancement of the elastic properties was found at low silica concentration. A model based on the radius of gyration of polymer matrix R-g and the mean distance between particles D is proposed to describe the interactions between polymer matrix and particles. When D is larger than 2R(g), the particles-polymer interactions are suggested to be responsible for the rheological properties. On the other side, when D is smaller than R-g, a silica network structure will be formed and the rheological properties of the composites are dominated by the interactions of particle-particle and particle-polymer. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Particle-reinforcement; Polymer-matrix composites (PMCs); Elasticity; Rheological properties

Wall slip of magnetorheological elastomers in parallel-plate rotational rheometry - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (7. TA Anwendertreffen Rheologie - Erlangen, 2015)

Ways to more potent capacitors for high-voltage DC transmission technology based on polymer nanocomposites and blends - Werner, Siegfried; Kaschta, Joachim; Schubert, Dirk W. (VDE High Voltage Technology, 2021)
To evaluate possible improvements of thin film capacitors, biaxial oriented films based on nanocomposites of PP and hydrophobic silica as well as polymer blends of PP and ENC were investigated. Therefore, the films were produced on a pilot scale stretching line, metallized and wound to capacitors. On scanning electron microscope (SEM) images the PP/ENC blends showed a layer like structure and the particles a homogeneous distribution throughout the film. The morphology of the PP matrix investigated by differential scanning calorimetry (DSC) was comparable for all films. Additionally, the degradation by compounding and processing was investigated using high temperature gel permeation chromatography (HT-GPC). A pronounced reduction of the molecular weight was found for the nanocomposites, as the particles were added in an additional compounding step. The suitability of the compounds for an application as capacitor films was evaluated determining dielectric strength and voltage endurance of the films as well as the reduction in capacitance and the increase in loss factor of the capacitors during an endurance test based on IEC 61071. It was revealed that the degradation of the molecular weight determined by HT-GPC was the governing factor for all four parameters. Among the different compounds the blend of PP and ENC was the most promising as it showed low degradation and a better voltage endurance than the PP reference. Nanoparticles might still be a viable option, however the degradation during compounding has to be reduced significantly.
CRIS-Team Scopus Importer:2021-03-12